Robustness and Mechanisms of the Atmospheric Response Over the Southern Ocean to Idealized Freshwater Input Around Antarctica - Xu, Xiaoqi; Martin, Torge; Beadling, Rebecca L.; Liu, Jiping; Bischof, Sabine; Hattermann, Tore; Huo, Wenjuan; Li, Qian; Marshall, John C.; Muilwijk, Morven; Pauling, Andrew G.; Purich, Ariaan; et al. (Geophysical Research Letters, 2025)
Enhanced Antarctic ice sheet mass loss yields ocean surface freshening, cooling and sea ice expansion, which result in changes in the atmospheric conditions. Using the Southern Ocean Freshwater Input from Antarctica (SOFIA) multi-model ensemble, we study the atmospheric response to a 100-year idealized freshwater release of 0.1 Sv. All models simulate a surface-intensified tropospheric cooling and lower-stratospheric warming south of 35°S. Tropospheric cooling is attributed to sea ice expansion and the associated albedo enhancement in winter and a colder sea surface in summer. This cooling yields a downward displacement of the tropopause, reduced stratospheric water vapor content and ultimately warming around 200 hPa. An enhanced southward eddy heat flux explains warming at 10?100 hPa during austral winter. Despite a temporally (and spatially) uniform prescribed freshwater flux, a prominent sea ice seasonal cycle and atmosphere dynamics result in a distinct seasonal pattern in the occurrence and magnitude of the temperature responses.
Keywords: Sørishavet; klimamodeller; klimatologi; oseanografi

Impacts of the CICE sea ice model and ERA atmosphere on an Antarctic MetROMS ocean model, MetROMS-UHel-v1.0 - Äijälä, C.; Nie, Y.; Gutiérrez-Loza, L.; De Falco, C.; Lauvset, S. K.; Cheng, B.; Bailey, D. A.; Uotila, P. (Geoscientific Model Development, 2025)
In recent years, the Antarctic sea ice has experienced major changes, which are neither well understood nor adequately reproduced by Earth system models. To support model development with an aim to improve Antarctic sea ice and upper-ocean predictions, the impacts of updating the sea ice model and the atmospheric forcing are investigated. In the new MetROMS-UHel-v1.0 (henceforth MetROMS-UHel) ocean–sea ice model, the sea ice component has been updated from CICE5 to CICE6, and the forcing has been updated from ERA-Interim (ERAI) to ERA5 reanalyses. The two versions of MetROMS evaluated in this study use a version of the regional ROMS ocean model including ice shelf cavities. We find that the update of CICE (Community Ice CodE) and ERA reduced the negative bias of the sea ice area in summer. However, the sea ice volume decreases after the CICE update but increases when the atmospheric forcing is updated. As a net result after both updates, the modelled sea ice becomes thinner and more deformed, particularly near the coast. The ROMS ocean model usually yielded a deeper ocean mixed layer compared to observations. Using ERA5, the situation was slightly improved. The update from CICE5 to CICE6 resulted in a fresher coastal ocean due to a smaller salt flux from sea ice to the ocean. In the ice shelf cavities, the modelled melt rates are generally underestimated compared with observations, with the largest underestimation coming from the ice shelves in the too cold Amundsen and Bellingshausen seas as well as from the Australian sector in East Antarctica. These identified sea ice and oceanic changes vary seasonally and regionally. By determining sea ice and oceanic changes after the model and forcing updates and evaluating them against observations, this study informs modellers on improvements and aspects requiring attention with potential model adjustments.
Keywords: Amundsenhavet; Bellingshausenhavet; Sørishavet; havis; klimaendringer; klimamodeller; klimatologi; meteorologi; sjøis

Antarctic Water Stable Isotopes in the Global Atmospheric Model LMDZ6: From Climatology to Boundary Layer Processes - Dutrievoz, Niels; Agosta, Cécile; Risi, Camille; Vignon, Étienne; Nguyen, Sébastien; Landais, Amaëlle; Fourré, Elise; Leroy-Dos Santos, Christophe; Casado, Mathieu; Masson-Delmotte, Valérie; Jouzel, Jean; Dubos, Thomas; et al. (Journal of Geophysical Research: Atmospheres, 2025)
Observations of water stable isotopes in Antarctic surface snow, precipitation and water vapor are key for improving our understanding of the atmospheric water cycle and past climate reconstructions from ice cores. In this study, we use isotopic observations in Antarctica to assess the skill of the isotope-enabled atmospheric general circulation model LMDZ6, nudged to ERA5 above the boundary layer (1980?2023 period). The model has no significant bias for time-mean temperature and snow accumulation over the ice sheet. Sensitivity test on parameterized supersaturation strength highlights its opposite effect on precipitation ${δ }^{18}$O and d-excess. Selecting an intermediate supersaturation strength resulted in a minimal bias for surface snow ${δ }^{18}$O across the continent, with a reduced but systematic positive bias in surface snow d-excess ( ${\sim} $5?). We then assessed seasonal and diurnal isotope variability with daily precipitation and continuous vapor isotopes at Dumont d?Urville (DDU, coastal station) and Concordia (inland station). On a seasonal scale, LMDZ6iso accurately reproduces the seasonal cycle of precipitation ${δ }^{18}$O and d-excess at both stations. Moving from statistical evaluation to physical analysis, we use the individual process contributions to boundary-layer water vapor isotopes to identify the main drivers controlling the clear-sky isotopic daily cycles. At Concordia, daily isotope variations are mainly driven by surface sublimation, whereas at DDU they are driven by surface sublimation and advection by the katabatic flow. Our results suggest that to further improve water isotopes in LMDZ6iso, fractionation during surface sublimation should be included and fractionation at condensation for low temperature should be better constrained.
Keywords: Antarktis; global klimamodell; iskjerner; klimamodeller; klimatologi; meteorologi; paleoklimatologi; vannstabile isotoper

Inferring the seasonality of sea ice floes in the Weddell Sea using ICESat-2 - Gupta, M.; Regan, H.; Koo, Y.; Chua, S. M. T.; Li, X.; Heil, P. (The Cryosphere, 2025)
Over the last decade, the Southern Ocean has experienced episodes of severe sea ice area decline. Abrupt events of sea ice loss are challenging to predict, in part due to incomplete understanding of processes occurring at the scale of individual ice floes. Here, we use high-resolution altimetry (ICESat-2) to quantify the seasonal life cycle of floes in the perennial sea ice pack of the Weddell Sea. The evolution of the floe chord distribution (FCD) shows an increase in the proportion of smaller floes between November and February, which coincides with the asymmetric melt–freeze cycle of the pack. The freeboard ice thickness distribution (fITD) suggests mirrored seasonality between the western and southern sections of the Weddell Sea ice cover, with an increasing proportion of thicker floes between October and March in the south and the opposite in the west. Throughout the seasonal cycle, there is a positive correlation between the mean chord length of floes and their average freeboard thickness. Composited floe profiles reveal that smaller floes are more vertically round than larger floes and that the mean roundness of floes increases during the melt season. These results show that regional differences in ice concentration and type at larger scales occur in conjunction with different behaviors at the small scale. We therefore suggest that floe-derived metrics obtained from altimetry could provide useful diagnostics for floe-aware models and improve our understanding of sea ice processes across scales.
Keywords: Sørishavet; Weddellhavet; fjernmåling; havis; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis

Local Drivers of Antarctic Spring Sea Ice Retreat - Himmich, Kenza; Vancoppenolle, Martin; Stammerjohn, Sharon; Bocquet, Marion; Madec, Gurvan; Fleury, Sara (Geophysical Research Letters, 2025)
Antarctic sea ice has changed significantly over the past four decades; yet limited understanding of fundamental processes, including its seasonal cycle, hinders our ability to interpret these changes. Here, we examine the processes determining the moment when sea ice locally disappears each spring, defined as the retreat date, using satellite observations over 1994?2020. We find that climatological retreat date is driven by sea ice melt in most of the seasonal ice zone and strongly constrained by the seasonal maximum ice thickness. Ice removal due to drifting ice export predominantly drives retreat only in coastal polynyas. At interannual timescales, retreat date anomalies are also preconditioned by prior maximum ice thickness, which affects melt-driven spring ice loss through the ice-albedo feedback, though this effect appears limited to specific regions. Winds emerge as a primary driver of interannual variability in the retreat date, influencing both drift- and melt-related spring ice removal processes.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; oseanografi; sjøis

Synoptic Drivers and Moisture Sources of Snowfall in Coastal Victoria Land, Antarctica - Hofsteenge, M. G.; Cullen, N. J.; Sodemann, H.; Katurji, M. (Journal of Geophysical Research: Atmospheres, 2025)
Snowfall is an important component of the mass balance of ice sheets and glaciers in Antarctica. In coastal Victoria Land (VL), changes to snowfall can impact ice masses, landscapes, and coastal ecosystems. Coastal VL is characterized by strong gradients in snowfall rates between the polar desert of the McMurdo Dry Valleys and the high accumulation in northern VL. Extreme precipitation events significantly contribute to total precipitation, with the largest contribution in the Terra Nova Bay area. We present a comprehensive analysis of snowfall dynamics in this region, using a Lagrangian moisture source diagnostic to study moisture sources and Self-Organizing Maps (SOM) to link these to different synoptic weather types. The moisture for snowfall in VL originates from the Southern Ocean, with more local sources in the Ross Sea embayment in summer when sea ice is reduced. We show a strong division in moisture sources between northern and southern VL, with the north receiving precipitation from moisture sources to the west and southern VL from the east. Precipitation in northern VL results from meridional transport of marine air from lower latitudes, while precipitation in southern VL is related to cyclonic disturbances in the Ross Sea that bring moisture from the east. Extreme precipitation in northern VL occurs during blocking highs that intensify meridional transport. Such intrusions of marine air, sometimes in the form of atmospheric rivers, do not impact the more isolated western Ross Ice Shelf and southern VL further in the Ross Sea embayment.
Keywords: Rosshavet; Sørishavet; havis; klimatologi; meteorologi; nedbør; sjøis

Giant iceberg meltwater increases upper-ocean stratification and vertical mixing - Lucas, Natasha S.; Brearley, J. Alexander; Hendry, Katharine R.; Spira, Theo; Braakmann-Folgmann, Anne; Abrahamsen, E. Povl; Meredith, Michael P.; Tarling, Geraint A. (Nature Geoscience, 2025)
Ice-sheet mass loss is one of the clearest manifestations of climate change, with Antarctica discharging mass into the ocean via melting or through calving. The latter produces icebergs that can modify ocean water properties, often at great distances from source. This affects upper-ocean physics and primary productivity, with implications for atmospheric carbon drawdown. A detailed understanding of iceberg modification of ocean waters has hitherto been hindered by a lack of proximal measurements. Here unique measurements of a giant iceberg from an underwater glider enable quantification of meltwater effects on the physical and biological processes in the upper layers of the Southern Ocean, a region disproportionately important for global heat and carbon sequestration. Iceberg basal melting erodes seasonally produced winter water layer stratification, normally forming a strong potential energy barrier to vertical exchange of surface and deep waters, while freshwater run-off increases and shoals near-surface stratification. Nutrient-rich deeper waters, incorporating meltwater loaded with terrigenous material, are ventilated to below this stratification maxima, providing a potential mechanism for alleviating critical phytoplankton-limiting components. Regional historical hydrographic data demonstrate similar stratification changes during the passage of another large iceberg, suggesting that they may be an important pathway of aseasonal winter water modification.
Keywords: Sørishavet; Weddellhavet; biogeokjemi; glasiologi; global oppvarming; hydrografi; klimaendringer; klimatologi; oseanografi

Katabatic and foehn winds control the distribution of supraglacial lakes in Dronning Maud Land, Antarctica - Mahagaonkar, Anirudha; Moholdt, Geir; Glaude, Quentin; Schuler, Thomas V. (Earth and Planetary Science Letters, 2025)
Meltwater ponding along the margins of Antarctica poses a threat to ice shelf stability, increasing the risk of accelerated inland ice mass loss. Understanding the key drivers of supraglacial lake formation is therefore essential for assessing the vulnerability and future stability of Antarctic ice shelves. In this study, we combine high-resolution simulation from the regional climate model Modèle Atmosphérique Régional (MAR) with satellite-derived records of supraglacial lakes in coastal Dronning Maud Land to investigate the role of topographic downslope winds on spatial lake distribution. We find that persistent katabatic winds and episodic foehn winds are key controls on the observed regional patterns of lakes. Katabatic winds, most persistent in eastern Dronning Maud Land, exert a sustained impact near grounding zones through snow erosion, scouring and sublimation. Foehn winds predominantly affect ice shelves on the lee (western) side of large ice rises and promontories, causing considerable surface warming. While these downslope winds directly contribute to surface melt and ponding during summer, they also precondition the surface year-round through wind-driven warming and sublimation. Statistical analysis of downslope wind exposure further allows us to identify other Antarctic ice shelves that may become vulnerable to future ponding as firn retention capacity is diminished.
Keywords: Dronning Maud Land; glasiologi; isshelf; klimamodeller; klimatologi; kryosfæren; meteorologi; subglasial innsjø

Controls of the global overturning circulation of the ocean - Roquet, Fabien; Bell, Michael J.; de Boer, Agatha M.; Ferreira, David; Jones, C. Spencer; LaCasce, Joseph H.; de Lavergne, Casimir; Marshall, David P.; Munday, David R.; Nycander, Jonas; Ödalen, Malin (npj Climate and Atmospheric Science, 2025)
The global overturning circulation (GOC) is the largest scale component of the ocean circulation, associated with a global redistribution of key tracers such as heat and carbon. The GOC generates decadal to millennial climate variability, and will determine much of the long-term response to anthropogenic climate perturbations. This review aims at providing an overview of the main controls of the GOC. By controls, we mean processes affecting the overturning structure and variability. We distinguish three main controls: mechanical mixing, convection, and wind pumping. Geography provides an additional control on geological timescales. An important emphasis of this review is to present how the different controls interact with each other to produce an overturning flow, making this review relevant to the study of past, present and future climates as well as to exoplanets’ oceans.
Keywords: Sørishavet; global klimamodell; klimamodeller; klimatologi; meteorologi; oseanografi; paleoseanografi

Modeling Antarctic Sea Ice Variability Using a Brittle Rheology - Santana, Rafael; Boutin, Guillaume; Horvat, Christopher; Ólason, Einar; Williams, Timothy; Rampal, Pierre (Journal of Advances in Modeling Earth Systems, 2025)
Sea ice is a composite solid material that sustains large fracture features at scales from meters to kilometres. These fractures can play an important role in coupled atmosphere-ocean processes. To model these features, brittle sea ice physics, via the Brittle-Bingham-Maxwell (BBM) rheology, has been implemented in the Lagrangian neXt generation Sea Ice Model (neXtSIM). In Arctic-only simulations, the BBM rheology has shown a capacity to represent observationally consistent sea ice fracture patterns and breakup across a wide range of time and length scales. Still, it has not been tested whether this approach is suitable for the modeling of Antarctic sea ice, which is thinner and more seasonal compared to Arctic sea ice, and whether the ability to reproduce sea ice fractures has an impact on simulating Antarctic sea ice properties. Here, we introduce a new 50-km grid-spacing Antarctic configuration of neXtSIM, neXtSIM-Ant, using the BBM rheology. We evaluate this simulation against observations of sea ice extent, drift, and thickness and compare it with identically-forced neXtSIM simulations that use the standard modified Elastic-Visco-Plastic (mEVP) rheology. In general, using BBM results in thicker sea ice and an improved correlation of sea ice drift with observations than mEVP. We suggest that this is related to short-duration breakup events caused by Antarctic storms that are not well-simulated in the viscous-plastic model.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Impact of Ocean, Sea Ice or Atmosphere Initialization on Seasonal Prediction of Regional Antarctic Sea Ice - Xiu, Yongwu; Wang, Yiguo; Luo, Hao; Garcia-Oliva, Lilian; Yang, Qinghua (Journal of Advances in Modeling Earth Systems, 2025)
Dynamical modeling is widely utilized for Antarctic sea ice prediction. However, the relative impact of initializing different model components remains unclear. We compare three sets of hindcasts of the Norwegian Climate Prediction Model (NorCPM), which are initialized by ocean, ocean/sea-ice, or atmosphere data and referred to as the OCN, OCNICE, and ATM hindcasts hereafter. The seasonal cycle of sea ice extent (SIE) in the ATM reanalysis shows a slightly better agreement with observations than the OCN and OCNICE reanalyzes. The trends of sea ice concentration (SIC) in the OCN and OCNICE reanalyzes compare well to observations, but the ATM reanalysis is poor over the western Antarctic. The OCNICE reanalysis yields the most accurate estimation of sea ice variability, while the OCN and ATM reanalyzes are comparable. Evaluation of the hindcasts reveals the predictive skill varies with region and season. Austral winter SIE of the western Antarctic can be skillfully predicted 12 months ahead, while the predictive skill in the eastern Antarctic is low. Austral winter SIE predictability can be largely attributed to high sea surface temperature predictability, thanks to skillful initialization of ocean heat content. The ATM hindcast from July or October performs best due to the effective initialization of sea-ice thickness, which enhances prediction skills until early austral summer via its long memory. Meanwhile, the stratosphere-troposphere coupling contributes to the prediction of springtime. The comparable skill between the OCN and OCNICE hindcasts implies limited benefits from SIC data on prediction when using ocean data.
Keywords: Sørishavet; atmosfæren; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Extended seasonal prediction of Antarctic sea ice concentration using ANTSIC-UNet - Yang, Z.; Liu, J.; Song, M.; Hu, Y.; Yang, Q.; Fan, K.; Graversen, R. G.; Zhou, L. (The Cryosphere, 2025)
Antarctic sea ice has experienced rapid change in recent years, with the total sea ice extent abruptly decreasing after a period of gradual increase from the late 1970s until 2014. Accurate long-term predictions of Antarctic sea ice concentration by dynamical or machine learning models are crucial for supporting the expanding activities in the Southern Ocean, related to for instance scientific research, tourism and fisheries. However, dynamical models often face difficulties in accurately predicting Antarctic sea ice due to limited representations of air-ice-sea interactions, especially on seasonal timescales and during the summer months. In addition, existing deep learning approaches typically rely on historical sea ice data, neglecting the complex interactions between sea ice and other climate variables, and lack interpretability of the underlying physical processes. Moreover, little attention has been paid to extended seasonal forecasts, and systematic evaluations of the predictive skill during extreme years remain scarce. To address these challenges and gaps, we here develop a deep learning model (named ANTSIC-UNet), trained by multiple climate variables, and evaluate its skill for extended up-to-six-months seasonal prediction of Antarctic sea ice concentration. We compare the predictive skill of ANTSIC-UNet in the Pan- and regional Antarctic with two benchmark models (a linear trend and an anomaly persistence model) and a dynamical model (SEAS5). In terms of root-mean-square error (RMSE) of sea ice concentration and integrated ice-edge error (IIEE), ANTSIC-UNet shows much better skills relative to the other models for the extended seasonal prediction, especially for the extreme events in recent years. Sea ice prediction errors increase with lead time, and are smaller during autumn and winter than in summer. The Pacific and Indian Oceans show accurate prediction performance at the sea ice edge during summer, and ANTSIC-UNet provides high predictive skill in capturing the interannual variability of Pan-Antarctic and regional sea ice extent anomalies. In addition, we quantify the importance of variables through a post-hoc interpretation method. This analysis suggests that the ANTSIC-UNet prediction at short lead times is sensitive to sea surface temperature, radiative flux, and atmospheric circulation in addition to sea ice conditions. At longer lead times, zonal wind in the stratosphere appears to be an important influencing factor for the prediction. Building on these findings, we further demonstrate that incorporating physical constraints into deep learning models potentially leads to a gain in the accuracy of the Antarctic sea ice edge prediction on extended seasonal timescales.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; kryosfæren; maskinlæring; oseanografi; sjøis

Sources of low-frequency variability in observed Antarctic sea ice - Bonan, D. B.; Dörr, J.; Wills, R. C. J.; Thompson, A. F.; Årthun, M. (The Cryosphere, 2024)
Antarctic sea ice has exhibited significant variability over the satellite record, including a period of prolonged and gradual expansion, as well as a period of sudden decline. A number of mechanisms have been proposed to explain this variability, but how each mechanism manifests spatially and temporally remains poorly understood. Here, we use a statistical method called low-frequency component analysis to analyze the spatiotemporal structure of observed Antarctic sea ice concentration variability. The identified patterns reveal distinct modes of low-frequency sea ice variability. The leading mode, which accounts for the large-scale, gradual expansion of sea ice, is associated with the Interdecadal Pacific Oscillation and resembles the observed sea surface temperature trend pattern that climate models have trouble reproducing. The second mode is associated with the central Pacific El Niño–Southern Oscillation (ENSO) and the Southern Annular Mode and accounts for most of the sea ice variability in the Ross Sea. The third mode is associated with the eastern Pacific ENSO and Amundsen Sea Low and accounts for most of the pan-Antarctic sea ice variability and almost all of the sea ice variability in the Weddell Sea. The third mode is also related to periods of abrupt Antarctic sea ice decline that are associated with a weakening of the circumpolar westerlies, which favors surface warming through a shoaling of the ocean mixed layer and decreased northward Ekman heat transport. Broadly, these results suggest that climate model biases in long-term Antarctic sea ice and large-scale sea surface temperature trends are related to each other and that eastern Pacific ENSO variability is a key ingredient for abrupt Antarctic sea ice changes.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; meteorologi; oseanografi; sjøis

Glacial–interglacial Circumpolar Deep Water temperatures during the last 800 000 years: estimates from a synthesis of bottom water temperature reconstructions - Chandler, D. M.; Langebroek, Petra M. (Clim. Past, 2024)
Future climate and sea level projections depend sensitively on the response of the Antarctic Ice Sheet to ocean-driven melting and the resulting freshwater fluxes into the Southern Ocean. Circumpolar Deep Water (CDW) transport across the Antarctic continental shelf and into cavities beneath ice shelves is increasingly recognised as a crucial heat source for ice shelf melt. Quantifying past changes in the temperature of CDW is therefore of great benefit for modelling ice sheet response to past warm climates, for validating paleoclimate models, and for putting recent and projected changes in CDW temperature into context. Here we compile the available bottom water temperature reconstructions representative of CDW over the past 800 kyr. Estimated interglacial warming reached anomalies of +0.6 +/- 0.4 degrees C (MIS 11) and +0.5 +/- 0.5 degrees C (MIS 5) relative to present. Glacial cooling typically reached anomalies of ca. -1.5 to -2 degrees C, therefore maintaining positive thermal forcing for ice shelf melt even during glacials in the Amundsen Sea region of West Antarctica. Despite high variance amongst a small number of records and poor (4 kyr) temporal resolution, we find persistent and close relationships between our estimated CDW temperature and Southern Ocean sea surface temperature, Antarctic surface air temperature, and global deep-water temperature reconstructions at glacial-cycle timescales. Given the important role that CDW plays in connecting the world's three main ocean basins and in driving Antarctic Ice Sheet mass loss, additional temperature reconstructions targeting CDW are urgently needed to increase temporal and spatial resolution and to decrease uncertainty in past CDW temperatures - whether for use as a boundary condition, for model validation, or for understanding past oceanographic changes.
Keywords: Sørishavet; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Early aerial expedition photos reveal 85 years of glacier growth and stability in East Antarctica - Dømgaard, Mads; Schomacker, Anders; Isaksson, Elisabeth; Millan, Romain; Huiban, Flora; Dehecq, Amaury; Fleischer, Amanda; Moholdt, Geir; Andersen, Jonas K.; Bjørk, Anders A. (Nature Communications, 2024)
During the last few decades, several sectors in Antarctica have transitioned from glacial mass balance equilibrium to mass loss. In order to determine if recent trends exceed the scale of natural variability, long-term observations are vital. Here we explore the earliest, large-scale, aerial image archive of Antarctica to provide a unique record of 21 outlet glaciers along the coastline of East Antarctica since the 1930s. In Lützow-Holm Bay, our results reveal constant ice surface elevations since the 1930s, and indications of a weakening of local land-fast sea-ice conditions. Along the coastline of Kemp and Mac Robertson, and Ingrid Christensen Coast, we observe a long-term moderate thickening of the glaciers since 1937 and 1960 with periodic thinning and decadal variability. In all regions, the long-term changes in ice thickness correspond with the trends in snowfall since 1940. Our results demonstrate that the stability and growth in ice elevations observed in terrestrial basins over the past few decades are part of a trend spanning at least a century, and highlight the importance of understanding long-term changes when interpreting current dynamics.
Keywords: Antarktis; Thorshavn ekspedisjon; flyfotografering; geografi; glasiologi; kartlegging; klimaendringer; klimatologi; kryosfæren; topografi

Observed water-mass characteristics and circulation off Prydz Bay, East Antarctica - Foppert, Annie; Bestley, Sophie; Shadwick, Elizabeth H.; Klocker, Andreas; Vives, Clara R.; Liniger, Guillaume; Westwood, Karen J. (Frontiers in Marine Science, 2024)
Circulation and water masses in the greater Prydz Bay region were surveyed in the austral summer 2021 (January-March) during the ‘Trends in Euphausiids off Mawson, Predators and Oceanography’ (TEMPO) experiment, and are described in this paper. The Southern Antarctic Circumpolar Current Front is found in the northern part of the survey area, generally near 63-64°S, whereas the Southern Boundary Front is located between 64 and 65.5°S. The westward flowing Antarctic Slope Front (ASF) is found in the southern part of the survey area near the continental slope on most transects. Highest concentrations of oxygen (> 300 µmol kg−1) are found in shelf waters at stations in Prydz Bay, south of 67°S along 75°E, whereas the lowest oxygen values are found in the Circumpolar Deep Water layer, with an average of roughly 215 µmol kg−1. North of the northern extension of the ASF, surface mixed layers are between 20 and 60 m deep. Mixed layers tend to deepen slightly in the northern part of the survey, generally increasing north of 64°S where the ocean has been ice-free the longest. We find evidence of upwelling of waters into the surface layers, based on temperature anomaly, particularly strong along 80°E. Enhanced variability of biogeochemical properties - nutrients, DIC, DO - in the AASW layer is driven by a combination of sea-ice and biological processes. Antarctic Bottom Water, defined as water with neutral density > 28.3 kg m-3, was sampled at all the offshore full-depth stations, with a colder/fresher variety along western transects and a warmer/saltier variety in the east. Newly formed Antarctic Bottom Water – the coldest, freshest, and most recently ventilated – is mostly found in the deep ocean along 65°E, in the base of the Daly Canyon.
Keywords: AABW; Sørishavet; klimatologi; oseanografi; vannmasser

An Assessment of Subseasonal Prediction Skill of the Antarctic Sea Ice Edge - Gao, Yuchun; Xiu, Yongwu; Nie, Yafei; Luo, Hao; Yang, Qinghua; Zampieri, Lorenzo; Lv, Xianqing; Uotila, Petteri (Journal of Geophysical Research: Oceans, 2024)
Abstract In this study, the subseasonal Antarctic sea ice edge prediction skill of the Copernicus Climate Change Service (C3S) and Subseasonal to Seasonal (S2S) projects was evaluated by a probabilistic metric, the spatial probability score (SPS). Both projects provide subseasonal to seasonal scale forecasts of multiple coupled dynamical systems. We found that predictions by individual dynamical systems remain skillful for up to 38 days (i.e., the ECMWF system). Regionally, dynamical systems are better at predicting the sea ice edge in the West Antarctic than in the East Antarctic. However, the seasonal variations of the prediction skill are partly system-dependent as some systems have a freezing-season bias, some had a melting-season bias, and some had a season-independent bias. Further analysis reveals that the model initialization is the crucial prerequisite for skillful subseasonal sea ice prediction. For those systems with the most realistic initialization, the model physics dictates the propagation of initialization errors and, consequently, the temporal length of predictive skill. Additionally, we found that the SPS-characterized prediction skill could be improved by increasing the ensemble size to gain a more realistic ensemble spread. Based on the C3S systems, we constructed a multi-model forecast from the above principles. This forecast consistently demonstrated a superior prediction skill compared to individual dynamical systems or statistical observation-based benchmarks. In summary, our results elucidate the most important factors (i.e., the model initialization and the model physics) affecting the currently available subseasonal Antarctic sea ice prediction systems and highlighting the opportunities to improve them significantly.
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; sjøis

The Use of Weather, Water, Ice, and Climate (WWIC) Information in the Polar Regions: What Is Known after the Decadelong Polar Prediction Project? - Heinrich, Victoria J.; Stewart, Emma J.; Liggett, Daniela; Carrasco, Jorge F.; Dawson, Jackie; Lamers, Machiel; Ljubicic, Gita J.; Jeuring, Jelmer; Thoman, Rick (Weather, Climate, and Society, 2024)
The polar regions are facing a wide range of compounding challenges, from climate change to increased human activity. Infrastructure, rescue services, and disaster response capabilities are limited in these remote environments. Relevant and usable weather, water, ice, and climate (WWIC) information is vital for safety, activity success, adaptation, and environmental protection. This has been a key focus for the World Meteorological Organization’s (WMO) Polar Prediction Project (PPP), and in particular its “Societal and Economic Research and Applications” (PPP-SERA) Task Team, which together over a decade have sought to understand polar WWIC information use in relation to operational needs, constraints, and decision contexts to inform the development of relevant services. To understand research progress and gaps on WWIC information use during the PPP (2013–23), we undertook a systematic bibliometric review of aligned scholarly peer-reviewed journal articles (n = 43), examining collaborations, topics, methods, and regional differences. Themes to emerge included activity and context, human factors, information needs, situational awareness, experience, local and Indigenous knowledge, and sharing of information. We observed an uneven representation of disciplinary backgrounds, geographic locations, research topics, and sectoral foci. Our review signifies an overall lack of Antarctic WWIC services research and a dominant focus on Arctic sea ice operations and risks. We noted with concern a mismatch between user needs and services provided. Our findings can help to improve WWIC services’ dissemination, communication effectiveness, and actionable knowledge provision for users and guide future research as the critical need for salient weather services across the polar regions remains beyond the PPP. Significance Statement Every day, people in the Arctic and Antarctic use weather, water, ice, and climate information to plan and carry out outdoor activities and operations in a safe way. Despite advances in numerical weather prediction, technology, and product development, barriers to accessing and effectively communicating high-quality usable observations, forecasts, and actionable knowledge remain. Poorer services, prediction accuracy, and interpretation are exacerbated by a lack of integrated social science research on relevant topics and a mismatch between the services provided and user needs. As a result, continued user engagement, research focusing on information use, risk communication, decision-making processes, and the application of science for services remain highly relevant to reducing risks and improving safety for people living, visiting, and working in the polar regions.
Keywords: Antarktis; klimaendringer; klimatologi; meteorologi; polarområdene

Ocean warming as a trigger for irreversible retreat of the Antarctic ice sheet - Hill, Emily A.; Gudmundsson, G. Hilmar; Chandler, David M. (Nature Climate Change, 2024)
Warmer ocean conditions could impact future ice loss from Antarctica due to their ability to thin and reduce the buttressing of laterally confined ice shelves. Previous studies highlight the potential for a cold to warm ocean regime shift within the sub-shelf cavities of the two largest Antarctic ice shelves—the Filchner–Ronne and Ross. However, how this impacts upstream ice flow and mass loss has not been quantified. Here using an ice sheet model and an ensemble of ocean-circulation model sub-shelf melt rates, we show that transition to a warm state in those ice shelf cavities leads to a destabilization and irreversible grounding line retreat in some locations. Once this ocean shift takes place, ice loss from the Filchner–Ronne and Ross catchments is greatly accelerated, and conditions begin to resemble those of the present-day Amundsen Sea sector—responsible for most current observed Antarctic ice loss—where this thermal shift has already occurred.
Keywords: Amundsenhavet; Antarktis; Sørishavet; global oppvarming; innlandsis; klimaendringer; klimatologi

SMOS-derived Antarctic thin sea ice thickness: data description and validation in the Weddell Sea - Kaleschke, L.; Tian-Kunze, X.; Hendricks, S.; Ricker, R. (Earth Syst. Sci. Data, 2024)
Accurate satellite measurements of the thickness of Antarctic sea ice are urgently needed but pose a particular challenge. The Antarctic data presented here were produced using a method to derive the sea ice thickness from 1.4 GHz brightness temperatures previously developed for the Arctic, with only modified auxiliary data. The ability to observe the thickness of thin sea ice using this method is limited to cold conditions, meaning it is only reasonable during the freezing period, typically March to October. The Soil Moisture and Ocean Salinity (SMOS) level-3 sea ice thickness product contains estimates of the sea ice thickness and its uncertainty up to a thickness of about 1 m. The sea ice thickness is provided as a daily average on a polar stereographic projection grid with a sample resolution of 12.5 km, while the SMOS brightness temperature data used have a footprint size of about 35–40 km in diameter. Data from SMOS have been available since 2010, and the mission's operation has been extended to continue until at least the end of 2025. Here we compare two versions of the SMOS Antarctic sea ice thickness product which are based on different level-1 input data (v3.2 based on SMOS L1C v620 and v3.3 based on SMOS L1C 724). A validation is performed to generate a first baseline reference for future improvements of the retrieval algorithm and synergies with other sensors. Sea ice thickness measurements to validate the SMOS product are particularly rare in Antarctica, especially during the winter season and for the valid range of thicknesses. From the available validation measurements, we selected datasets from the Weddell Sea that have varying degrees of representativeness: Helicopter-based EM Bird (HEM), Surface and Under-Ice Trawl (SUIT), and stationary Upward-Looking Sonars (ULS). While the helicopter can measure hundreds of kilometres, SUIT's use is limited to distances of a few kilometres and thus only captures a small fraction of an SMOS footprint. Compared to SMOS, the ULS are point measurements and multi-year time series are necessary to enable a statistically representative comparison. Only four of the ULS moorings have a temporal overlap with SMOS in the year 2010. Based on selected averaged HEM flights and monthly ULS climatologies, we find a small mean difference (bias) of less than 10 cm and a root mean square deviation of about 20 cm with a correlation coefficient R > 0.9 for the valid sea ice thickness range between 0 and about 1 m. The SMOS sea ice thickness showed an underestimate of about 40 cm with respect to the less representative SUIT validation data in the marginal ice zone. Compared with sea ice thickness outside the valid range, we find that SMOS strongly underestimates the real values, which underlines the need for combination with other sensors such as altimeters. In summary, the overall validity of the SMOS sea ice thickness for thin sea ice up to a thickness of about 1 m has been demonstrated through validation with multiple datasets. To ensure the quality of the SMOS product, an independent regional sea ice extent index was used for control. We found that the new version, v3.3, is slightly improved in terms of completeness, indicating fewer missing data. However, it is worth noting that the general characteristics of both datasets are very similar, also with the same limitations.
Keywords: Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; sjøis

Hydrography and circulation below Fimbulisen Ice Shelf, East Antarctica, from 14 years of moored observations - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Fransson, Agneta (Ocean Sci., 2024)
Future mass loss from the East Antarctic Ice Sheet represents a major uncertainty in projections of future sea level rise. Recent studies have highlighted the potential vulnerability of the East Antarctic Ice Sheet to atmospheric and oceanic changes, but long-term observations inside the ice shelf cavities are rare. Here, we present new insights from observations from three oceanic moorings below Fimbulisen Ice Shelf from 2009 to 2023. We examine the characteristics of intrusions of modified Warm Deep Water (mWDW) across a sill connecting the cavity to the open ocean and investigate seasonal variability of the circulation and water masses inside the cavity using an optimum multiparameter analysis. In autumn, the water below the 345 m deep central part of the ice shelf is composed of up to 30 % solar-heated, buoyant Antarctic Surface Water (ASW), separating colder Ice Shelf Water from the ice base and affecting the cavity circulation on seasonal timescales. At depth, the occurrence of mWDW is associated with the advection of cyclonic eddies across the sill into the cavity. These eddies reach up to the ice base. The warm intrusions are observed most often from January to March and from September to November, and traces of mWDW-derived meltwater close to the ice base imply an overturning of these warm intrusions inside the cavity. We suggest that this timing is set by both the offshore thermocline depth and the interactions of the Antarctic Slope Current with the ice shelf topography over the continental slope. Our findings provide a better understanding of the interplay between shallow inflows of ASW contributions and deep inflows of mWDW for basal melting at Fimbulisen Ice Shelf, with implications for the potential vulnerability of the ice shelf to climate change.
Keywords: Dronning Maud Land; hydrografi; isshelf; klimaendringer; klimatologi; oseanografi

The case for a Framework for UnderStanding Ice-Ocean iNteractions (FUSION) in the Antarctic-Southern Ocean system - McCormack, Felicity S.; Cook, Sue; Goldberg, Daniel N.; Nakayama, Yoshihiro; Seroussi, Hélène; Nias, Isabel; An, Lu; Slater, Donald; Hattermann, Tore (Elementa: Science of the Anthropocene, 2024)
We are in a period of rapidly accelerating change across the Antarctic continent and Southern Ocean, with land ice loss leading to sea level rise and multiple other climate impacts. The ice-ocean interactions that dominate the current ice loss signal are a key underdeveloped area of knowledge. The paucity of direct and continuous observations leads to high uncertainty in the glaciological, oceanographic and atmospheric fields required to constrain ice-ocean interactions, and there is a lack of standardised protocols for reconciling observations across different platforms and technologies and modelled outputs. Funding to support observational campaigns is under increasing pressure, including for long-term, internationally coordinated monitoring plans for the Antarctic continent and Southern Ocean. In this Practice Bridge article, we outline research priorities highlighted by the international ice-ocean community and propose the development of a Framework for UnderStanding Ice-Ocean iNteractions (FUSION), using a combined observational-modelling approach, to address these issues. Finally, we propose an implementation plan for putting FUSION into practice by focusing first on an essential variable in ice-ocean interactions: ocean-driven ice shelf melt.
Keywords: Antarktis; Sørishavet; glasiologi; innlandsis; klimamodeller; klimatologi; oseanografi

Highly stratified mid-Pliocene Southern Ocean in PlioMIP2 - Weiffenbach, J. E.; Dijkstra, H. A.; von der Heydt, A. S.; Abe-Ouchi, A.; Chan, W.-L.; Chandan, D.; Feng, R.; Haywood, A. M.; Hunter, S. J.; Li, X.; Otto-Bliesner, B. L.; Peltier, W. R.; et al. (Clim. Past, 2024)
During the mid-Pliocene warm period (mPWP; 3.264–3.025 Ma), atmospheric CO2 concentrations were approximately 400 ppm, and the Antarctic Ice Sheet was substantially reduced compared to today. Antarctica is surrounded by the Southern Ocean, which plays a crucial role in the global oceanic circulation and climate regulation. Using results from the Pliocene Model Intercomparison Project (PlioMIP2), we investigate Southern Ocean conditions during the mPWP with respect to the pre-industrial period. We find that the mean sea surface temperature (SST) warming in the Southern Ocean is 2.8 °C, while global mean SST warming is 2.4 °C. The enhanced warming is strongly tied to a dramatic decrease in sea ice cover over the mPWP Southern Ocean. We also see a freshening of the ocean (sub)surface, driven by an increase in precipitation over the Southern Ocean and Antarctica. The warmer and fresher surface leads to a highly stratified Southern Ocean that can be related to weakening of the deep abyssal overturning circulation. Sensitivity simulations show that the decrease in sea ice cover and enhanced warming is largely a consequence of the reduction in the Antarctic Ice Sheet. In addition, the mPWP geographic boundary conditions are responsible for approximately half of the increase in mPWP SST warming, sea ice loss, precipitation, and stratification increase over the Southern Ocean. From these results, we conclude that a strongly reduced Antarctic Ice Sheet during the mPWP has a substantial influence on the state of the Southern Ocean and exacerbates the changes that are induced by a higher CO2 concentration alone. This is relevant for the long-term future of the Southern Ocean, as we expect melting of the western Antarctic Ice Sheet in the future, an effect that is not currently taken into account in future projections by Coupled Model Intercomparison Project (CMIP) ensembles.
Keywords: Sørishavet; geologi; klimamodeller; klimatologi; oseanografi; paleoklimatologi

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Internal Ocean Dynamics Control the Long-Term Evolution of Weddell Sea Polynya Activity - Rheinlænder, Jonathan W.; Smedsrud, Lars H.; Nisanciouglu, Kerim H. (Frontiers in Climate, 2021)
Open-ocean polynyas effectively couple the ocean and atmosphere through large ice-free areas within the sea-ice cover, release vast quantities of oceanic heat, and impact deep ocean ventilation. Changes in polynya activity, particularly in the Weddell Sea, may be key to longer time-scale climate fluctuations, feedbacks and abrupt change. While changes in the occurrence of Weddell Sea polynyas are generally attributed to changes in the atmospheric surface forcing, the role of internal ocean dynamics for polynya variability is not well-resolved. In this study we employ a global coupled ocean-sea ice model with a repeating annual atmospheric cycle to explore changes in Weddell Sea water mass properties, stratification and ocean circulation driven by open-ocean polynyas. During the 1300-year long simulation, two large polynyas occur in the central Weddell Sea. Our results suggest that Weddell polynyas may be triggered without inter-annual changes in the atmospheric forcing. This highlights the role of ocean processes in preconditioning and triggering open-ocean polynyas on multi-centennial time-scales. The simulated polynyas form due to internal ocean-sea ice dynamics associated with a slow build-up and subsequent release of subsurface heat. A strong stratification and weak vertical mixing is necessary for building the subsurface heat reservoir. Once the water column turns unstable, enhanced vertical mixing of warm and saline waters into the surface layer causes efficient sea ice melt and the polynya appears. Subsequent, vigorous deep convection is maintained through upwelling of warm deep water leading to enhanced bottom water formation. We find a cessation of simulated deep convection and polynya activity due to long-term cooling and freshening of the subsurface heat reservoir. As subsurface waters in the Southern Ocean are now becoming warmer and saltier, we speculate that larger and more persistent Weddell polynyas could become more frequent in the future.
Keywords: Sørishavet; havis; klimamodeller; klimatologi; polynja; sjøis

Hvordan vet vi det vi vet om global oppvarming? - Seip, Knut Lehre (Naturen, 2021)
Hvordan vet vi det vi vet om global oppvarming? Denne artikkelen diskuterer grunnlaget for det vi vet med stor sikkerhet. I artikkelen diskuterer vi 12 temaer, og velger ut én eller to metoder som illustrerer hvordan kunnskap er skaffet til veie for hvert av temaene.
Keywords: Antarktis; global oppvarming; klimaendringer; klimatologi; polarområdene

Meridional Ocean Carbon Transport - Aldama-Campino, Aitor; Fransner, Filippa; Ödalen, Malin; Groeskamp, Sjoerd; Yool, Andrew; Döös, Kristofer; Nycander, Jonas (Global Biogeochemical Cycles, 2020)
The ocean's ability to take up and store CO2 is a key factor for understanding past and future climate variability. However, qualitative and quantitative understanding of surface-to-interior pathways, and how the ocean circulation affects the CO2 uptake, is limited. Consequently, how changes in ocean circulation may influence carbon uptake and storage and therefore the future climate remains ambiguous. Here we quantify the roles played by ocean circulation and various water masses in the meridional redistribution of carbon. We do so by calculating streamfunctions defined in dissolved inorganic carbon (DIC) and latitude coordinates, using output from a coupled biogeochemical-physical model. By further separating DIC into components originating from the solubility pump and a residual including the biological pump, air-sea disequilibrium, and anthropogenic CO2, we are able to distinguish the dominant pathways of how carbon enters particular water masses. With this new tool, we show that the largest meridional carbon transport occurs in a pole-to-equator transport in the subtropical gyres in the upper ocean. We are able to show that this pole-to-equator DIC transport and the Atlantic meridional overturning circulation (AMOC)-related DIC transport are mainly driven by the solubility pump. By contrast, the DIC transport associated with deep circulation, including that in Antarctic bottom water and Pacific deep water, is mostly driven by the biological pump. As these two pumps, as well as ocean circulation, are widely expected to be impacted by anthropogenic changes, these findings have implications for the future role of the ocean as a climate-buffering carbon reservoir.
Keywords: Sørishavet; biogeokjemi; bunnvann; karbon syklus; karbondioksid; klimatologi; oseanografi; vannmasser

CO2 Increase Experiments Using the CESM: Relationship to Climate Sensitivity and Comparison of CESM1 to CESM2 - Bacmeister, Julio; Hannay, Cecile; Medeiros, Brian; Gettelman, Andrew; Neale, Richard; Fredriksen, Hege-Beate; Lipscomb, William H; Simpson, Isla; Bailey, David; Holland, Marika; Lindsay, Keith; Otto-Bliesner, Bette (Journal of Advances in Modeling Earth Systems, 2020)
We examine the response of the Community Earth System Model Versions 1 and 2 (CESM1 and CESM2) to abrupt quadrupling of atmospheric CO2 concentrations (4xCO2) and to 1% annually increasing CO2 concentrations (1%CO2). Different estimates of equilibrium climate sensitivity (ECS) for CESM1 and CESM2 are presented. All estimates show that the sensitivity of CESM2 has increased by 1.5 K or more over that of CESM1. At the same time the transient climate response (TCR) of CESM1 and CESM2 derived from 1%CO2 experiments has not changed significantly—2.1 K in CESM1 and 2.0 K in CESM2. Increased initial forcing as well as stronger shortwave radiation feedbacks are responsible for the increase in ECS seen in CESM2. A decomposition of regional radiation feedbacks and their contribution to global feedbacks shows that the Southern Ocean plays a key role in the overall behavior of 4xCO2 experiments, accounting for about 50% of the total shortwave feedback in both CESM1 and CESM2. The Southern Ocean is also responsible for around half of the increase in shortwave feedback between CESM1 and CESM2, with a comparable contribution arising over tropical ocean. Experiments using a thermodynamic slab-ocean model (SOM) yield estimates of ECS that are in remarkable agreement with those from fully coupled Earth system model (ESM) experiments for the same level of CO2 increase. Finally, we show that the similarity of TCR in CESM1 and CESM2 masks significant regional differences in warming that occur in the 1%CO2 experiments for each model.
Keywords: Sørishavet; atmosfæren; fysikk; karbondioksid; klimaendringer; klimagasser; klimamodeller; klimatologi; menneskelig påvirkning; meteorologi; skyer

Full-Depth Global Estimates of Ocean Mesoscale Eddy Mixing From Observations and Theory - Groeskamp, Sjoerd; LaCasce, Joseph H; McDougall, Trevor J; Rogé, Marine (Geophysical Research Letters, 2020)
Mixing by mesoscale eddies profoundly impacts climate and ecosystems by redistributing and storing dissolved tracers such as heat and carbon. Eddy mixing is parameterized in most numerical models of the ocean and climate. To reduce known sensitivity to such parameterizations, observational estimates of mixing are needed. However, logistical and technological limitations obstruct our ability to measure global time-varying mixing rates. Here, we extend mixing length theory with mean-flow suppression theory, and first surface modes, to estimate mixing from readily available observational-based climatological data, of salinity, temperature, pressure, and eddy kinetic energy at the sea surface. The resulting full-depth global maps of eddy mixing can reproduce the few available direct estimates and confirm the importance of mean-flow suppression of mixing. The results also emphasize the significant effect of eddy surface intensification and its relation to the vertical density stratification. These new insights in mixing dynamics will improve future mesoscale eddy mixing parameterizations.
Keywords: Sørishavet; geovitenskap; havet; klimatologi; polarområdene; vannvirvler; økosystemer

The Role of Tides in Ocean-Ice Shelf Interactions in the Southwestern Weddell Sea - Hausmann, Ute; Sallée, Jean-Baptiste; Jourdain, Nicolas; Mathiot, Pierre; Rousset, Clément; Madec, Gurvan; Deshayes, Julie; Hattermann, Tore (Journal of Geophysical Research: Oceans, 2020)
To investigate the role of tides in Weddell Sea ocean-ice shelf melt interactions, and resulting consequences for ocean properties and sea ice interactions, we develop a regional ocean-sea ice model configuration, with time-varying ocean boundary and atmospheric forcing, including the deep open ocean (at 2.5–4 km horizontal resolution), the southwestern continental shelf (≈2.5 km), and the adjacent cavities of eastern Weddell, Larsen, and Filchner-Ronne ice shelves (FRIS, 1.5–2.5 km). Simulated circulation, water mass, and ice shelf melt properties compare overall well with available open ocean and cavity observational knowledge. Tides are shown to enhance the kinetic energy of the time-varying flow in contact with the ice shelves, thereby increasing melt. This dynamically driven impact of tides on net melting is to almost 90% compensated by cooling through the meltwater that is produced but not quickly exported from regions of melting in the Weddell Sea cold-cavity regime. The resulting systematic tide-driven enhancement of both produced meltwater and its refreezing on ascending branches of, especially the FRIS, cavity circulation acts to increase net ice shelf melting (by 50% in respect to the state without tides, ≈50 Gt yr−1). In addition, tides also increase the melt-induced FRIS cavity circulation, and the meltwater export by the FRIS outflow. Simulations suggest attendant changes on the open-ocean southwestern continental shelf, characterized by overall freshening and small year-round sea ice thickening, as well as in the deep southwestern Weddell Sea in the form of a marked freshening of newly formed bottom waters.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; havis; isbrem; isshelf; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis; tidevann

Validation of the TROPOspheric Monitoring Instrument (TROPOMI) surface UV radiation product - Lakkala, Kaisa; Kujanpää, Jukka; Brogniez, Colette; Henriot, Nicolas; Arola, Antti; Aun, Margit; Auriol, Frédérique; Bais, Alkiviadis F; Bernhard, Germar; De Bock, Veerle; Catalfamo, Maxime; Deroo, Christine; et al. (Atmos. Meas. Tech., 2020)
The TROPOspheric Monitoring Instrument (TROPOMI) onboard the Sentinel-5 Precursor (S5P) satellite was launched on 13 October 2017 to provide the atmospheric composition for atmosphere and climate research. The S5P is a Sun-synchronous polar-orbiting satellite providing global daily coverage. The TROPOMI swath is 2600 km wide, and the ground resolution for most data products is 7.2×3.5 km2 (5.6×3.5 km2 since 6 August 2019) at nadir. The Finnish Meteorological Institute (FMI) is responsible for the development of the TROPOMI UV algorithm and the processing of the TROPOMI surface ultraviolet (UV) radiation product which includes 36 UV parameters in total. Ground-based data from 25 sites located in arctic, subarctic, temperate, equatorial and Antarctic areas were used for validation of the TROPOMI overpass irradiance at 305, 310, 324 and 380 nm, overpass erythemally weighted dose rate/UV index, and erythemally weighted daily dose for the period from 1 January 2018 to 31 August 2019. The validation results showed that for most sites 60 %–80 % of TROPOMI data was within ±20 % of ground-based data for snow-free surface conditions. The median relative differences to ground-based measurements of TROPOMI snow-free surface daily doses were within ±10 % and ±5 % at two-thirds and at half of the sites, respectively. At several sites more than 90 % of cloud-free TROPOMI data was within ±20 % of ground-based measurements. Generally median relative differences between TROPOMI data and ground-based measurements were a little biased towards negative values (i.e. satellite data < ground-based measurement), but at high latitudes where non-homogeneous topography and albedo or snow conditions occurred, the negative bias was exceptionally high: from −30 % to −65 %. Positive biases of 10 %–15 % were also found for mountainous sites due to challenging topography. The TROPOMI surface UV radiation product includes quality flags to detect increased uncertainties in the data due to heterogeneous surface albedo and rough terrain, which can be used to filter the data retrieved under challenging conditions.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi; ultrafiolett stråling

CloudSat-Inferred Vertical Structure of Snowfall Over the Antarctic Continent - Lemonnier, Florentin; Madeleine, Jean-Baptiste; Claud, Chantal; Palerme, Cyril; Genthon, Christophe; L'Ecuyer, Tristan; Wood, Norman B (Journal of Geophysical Research: Atmospheres, 2020)
Current global warming is causing significant changes in snowfall in polar regions, directly impacting the mass balance of the ice caps. The only water supply in Antarctica, precipitation, is poorly estimated from surface measurements. The onboard cloud-profiling radar of the CloudSat satellite provided the first real opportunity to estimate solid precipitation at continental scale. Based on CloudSat observations, we propose to explore the vertical structure of precipitation in Antarctica over the 2007–2010 period. A first division of this data set following a topographical approach (continent vs. peripheral regions, with a 2,250 m topographical criterion) shows a high snowfall rate (275 mm yr at 1,200 m above ground level) with low relative seasonal variation ( ) over the peripheral areas. Over the plateau, the snowfall rate is low (34 mm yr at 1,200 m above ground level) with a much larger relative seasonal variation ( ). A second study that follows a geographical division highlights the average vertical structure of precipitation and temperature depending on the regions and their interactions with topography. In particular, over ice shelves, we see a strong dependence of the distribution of snowfall on the sea ice coverage. Finally, the relationship between precipitation and temperature is analyzed and compared with a simple analytical relationship. This study highlights that precipitation is largely dependent on the advection of air masses along the topographic slopes with an average vertical wind of 0.02 m s . This provides new diagnostics to evaluate climate models with a three-dimensional approach of the atmospheric structure of precipitation.
Keywords: Antarktis; global oppvarming; klimamodeller; klimatologi; meteorologi; nedbør; polarområdene; snøfall

Will Climate Change Impact Polar NOx Produced by Energetic Particle Precipitation? - Maliniemi, Ville; Marsh R., Daniel; Tyssøy, Hilde Nesse; Smith-Johnsen, Christine (Geophysical Research Letters, 2020)
Energetic electron precipitation (EEP) is an important source of polar nitrogen oxides (NOx) in the upper atmosphere. During winter, mesospheric NOx has a long chemical lifetime and is transported to the stratosphere by the mean meridional circulation. Climate change is expected to accelerate this circulation and therefore increase polar mesospheric descent rates. We investigate the Southern Hemispheric polar NOx distribution during the 21st century under a variety of future scenarios using simulations of the Whole Atmosphere Community Climate Model (WACCM). We simulate stronger polar mesospheric descent in all future scenarios that increase the atmospheric radiative forcing. Polar NOx in the upper stratosphere is significantly enhanced in two future scenarios with the largest increase in radiative forcing. This indicates that the ozone depleting NOx cycle will become more important in the future, especially if stratospheric chlorine species decline. Thus, EEP-related atmospheric effects may become more prominent in the future.
Keywords: Antarktis; geofysikk; klimaendringer; klimatologi; ozonlaget; polarområdene; romvitenskap

Modeling of the Influence of Sea Ice Cycle and Langmuir Circulation on the Upper Ocean Mixed Layer Depth and Freshwater Distribution at the West Antarctic Peninsula - Schultz, Cristina; Doney, Scott C.; Zhang, Weifeng Gordon; Regan, Heather; Holland, Paul R.; Meredith, Michael P.; Stammerjohn, Sharon (Journal of Geophysical Research: Oceans, 2020)
The Southern Ocean is chronically undersampled due to its remoteness, harsh environment, and sea ice cover. Ocean circulation models yield significant insight into key processes and to some extent obviate the dearth of data; however, they often underestimate surface mixed layer depth (MLD), with consequences for surface water-column temperature, salinity, and nutrient concentration. In this study, a coupled circulation and sea ice model was implemented for the region adjacent to the West Antarctic Peninsula, a climatically sensitive region which has exhibited decadal trends towards higher ocean temperature, shorter sea ice season, and increasing glacial freshwater input, overlain by strong interannual variability. Hindcast simulations were conducted with different air-ice drag coefficients and Langmuir circulation parameterizations to determine the impact of these factors on MLD. Including Langmuir circulation deepened the surface mixed layer, with the deepening being more pronounced in the shelf and slope regions. Optimal selection of an air-ice drag coefficient also increased modeled MLD by similar amounts and had a larger impact in improving the reliability of the simulated MLD interannual variability. This study highlights the importance of sea ice volume and redistribution to correctly reproduce the physics of the underlying ocean, and the potential of appropriately parameterizing Langmuir circulation to help correct for biases towards shallow MLD in the Southern Ocean. The model also reproduces observed freshwater patterns in the West Antarctic Peninsula during late summer and suggests that areas of intense summertime sea ice melt can still show net annual freezing due to high sea ice formation during the winter.
Keywords: Sørishavet; havis; klimatologi; langmuirsirkulasjon; oseanografi; sjøis

Two-Timescale Carbon Cycle Response to an AMOC Collapse - Nielsen, Søren B; Jochum, Markus; Pedro, Joel B; Eden, Carsten; Nuterman, Roman (Paleoceanography and Paleoclimatology, 2019)
Atmospheric CO2 concentrations (pCO2) varied on millennial timescales in phase with Antarctic temperature during the last glacial period. A prevailing view has been that carbon release and uptake by the Southern Ocean dominated this millennial-scale variability in pCO2. Here, using Earth System Model experiments with an improved parameterization of ocean vertical mixing, we find a major role for terrestrial and oceanic carbon releases in driving the pCO2 trend. In our simulations, a change in Northern Hemisphere insolation weakens the Atlantic Meridional Overturning Circulation (AMOC) leading to increasing pCO2 and Antarctic temperatures. The simulated rise in pCO2 is caused in equal parts by increased CO2 outgassing from the global ocean due to a reduced biological activity and changed ventilation rates, and terrestrial carbon release as a response to southward migration of the Intertropical Convergence Zone. The simulated terrestrial release of carbon could explain stadial declines in organic carbon reservoirs observed in recent ice core δ13C measurements. Our results show that parallel variations in Antarctic temperature and pCO2 do not necessitate that the Southern Ocean dominates carbon exchange; instead, changes in carbon flux from the global ocean and land carbon reservoirs can explain the observed pCO2 (and δ13C) changes.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; paleoklimatologi; paleoseanografi; temperatur

Topographic Shelf Waves Control Seasonal Melting Near Antarctic Ice Shelf Grounding Lines - Sun, Sainan; Hattermann, Tore; Pattyn, Frank; Nicholls, Keith W; Drews, Reinhard; Berger, Sophie (Geophysical Research Letters, 2019)
The buttressing potential of ice shelves is modulated by changes in subshelf melting, in response to changing ocean conditions. We analyze the temporal variability in subshelf melting using an autonomous phase-sensitive radio-echo sounder near the grounding line of the Roi Baudouin Ice Shelf in East Antarctica. When combined with additional oceanographic evidence of seasonal variations in the stratification and the amplification of diurnal tides around the shelf break topography (Gunnerus Bank), the results suggest an intricate mechanism in which topographic waves control the seasonal melt rate variability near the grounding line. This mechanism has not been considered before and has the potential to enhance local melt rates without advecting different water masses. As topographic waves seem to strengthen in a stratified ocean, the freshening of Antarctic surface water, predicted by observations and models, is likely to increase future basal melting in this area.
Keywords: Sørishavet; glasiologi; isshelf; klimatologi; oseanografi; smelting; vannmasser

Verification and Improvement of the Ability of CFSv2 to Predict the Antarctic Oscillation in Boreal Spring - Zhang, Dapeng; Huang, Yanyan; Sun, Bo; Li, Fei; Wang, Huijun (Advances in Atmospheric Sciences, 2019)
The boreal spring Antarctic Oscillation (AAO) has a significant impact on the spring and summer climate in China. This study evaluates the capability of the NCEP’s Climate Forecast System, version 2 (CFSv2), in predicting the boreal spring AAO for the period 1983–2015. The results indicate that CFSv2 has poor skill in predicting the spring AAO, failing to predict the zonally symmetric spatial pattern of the AAO, with an insignificant correlation of 0.02 between the predicted and observed AAO Index (AAOI). Considering the interannual increment approach can amplify the prediction signals, we firstly establish a dynamical–statistical model to improve the interannual increment of the AAOI (DY AAOI), with two predictors of CFSv2-forecasted concurrent spring sea surface temperatures and observed preceding autumn sea ice. This dynamical–statistical model demonstrates good capability in predicting DY AAOI, with a significant correlation coefficient of 0.58 between the observation and prediction during 1983–2015 in the two-year-out cross-validation. Then, we obtain an improved AAOI by adding the improved DY AAOI to the preceding observed AAOI. The improved AAOI shows a significant correlation coefficient of 0.45 with the observed AAOI during 1983–2015. Moreover, the unrealistic atmospheric response to March–April–May sea ice in CFSv2 may be the possible cause for the failure of CFSv2 to predict the AAO. This study gives new clues regarding AAO prediction and short-term climate prediction.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi

On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap

A Model-Based Evaluation of the Inverse Gaussian Transit-Time Distribution Method for Inferring Anthropogenic Carbon Storage in the Ocean - He, Yan-Chun; Tjiputra, Jerry; Langehaug, Helene R.; Jeansson, Emil; Gao, Yongqi; Schwinger, Jörg; Olsen, Are (Journal of Geophysical Research: Oceans, 2018)
The Inverse Gaussian approximation of transit time distribution method (IG-TTD) is widely used to infer the anthropogenic carbon (Cant) concentration in the ocean from measurements of transient tracers such as chlorofluorocarbons (CFCs) and sulfur hexafluoride (SF6). Its accuracy relies on the validity of several assumptions, notably (i) a steady state ocean circulation, (ii) a prescribed age tracer saturation history, e.g., a constant 100% saturation, (iii) a prescribed constant degree of mixing in the ocean, (iv) a constant surface ocean air-sea CO2 disequilibrium with time, and (v) that preformed alkalinity can be sufficiently estimated by salinity or salinity and temperature. Here, these assumptions are evaluated using simulated “model-truth” of Cant. The results give the IG-TTD method a range of uncertainty from 7.8% to 13.6% (11.4 Pg C to 19.8 Pg C) due to above assumptions, which is about half of the uncertainty derived in previous model studies. Assumptions (ii), (iv) and (iii) are the three largest sources of uncertainties, accounting for 5.5%, 3.8% and 3.0%, respectively, while assumptions (i) and (v) only contribute about 0.6% and 0.7%. Regionally, the Southern Ocean contributes the largest uncertainty, of 7.8%, while the North Atlantic contributes about 1.3%. Our findings demonstrate that spatial-dependency of , and temporal changes in tracer saturation and air-sea CO2 disequilibrium have strong compensating effect on the estimated Cant. The values of these parameters should be quantified to reduce the uncertainty of IG-TTD; this is increasingly important under a changing ocean climate.
Keywords: Sørishavet; antropogenisk CO2; fossilt brensel; karbondioksid; karbonlagring; klimaendringer; klimatologi

Basal Melt and Freezing Rates From First Noble Gas Samples Beneath an Ice Shelf - Huhn, Oliver; Hattermann, Tore; Davis, Peter E D; Dunker, Erich; Hellmer, Hartmut H; Nicholls, Keith W; Østerhus, Svein; Rhein, Monika; Schröder, Michael; Sültenfuß, Jürgen (Geophysical Research Letters, 2018)
A climatically induced acceleration in ocean-driven melting of Antarctic ice shelves would have consequences for both the discharge of continental ice into the ocean and thus global sea level, and for the formation of Antarctic Bottom Water and the oceanic meridional overturning circulation. Using a novel gas-tight in situ water sampler, noble gas samples have been collected from six locations beneath the Filchner Ice Shelf, the first such samples from beneath an Antarctic ice shelf. Helium and neon are uniquely suited as tracers of glacial meltwater in the ocean. Basal meltwater fractions range from 3.6% near the ice shelf base to 0.5% near the sea floor, with distinct regional differences. We estimate an average basal melt rate for the Filchner-Ronne Ice Shelf of 177 ± 95 Gt/year, independently confirming previous results. We calculate that up to 2.7% of the meltwater has been refrozen, and we identify a local source of crustal helium.
Keywords: Sørishavet; Weddellhavet; bunnvann; glasiologi; havnivå; innlandsis; isbrem; klimatologi; oseanografi; smelting; vannmasser

Observations of Ice Nucleating Particles Over Southern Ocean Waters - McCluskey, Christina S; Hill, Thomas C J; Humphries, Ruhi S; Rauker, Anne M; Moreau, Sebastien; Strutton, P G; Chambers, Scott Dudley; Williams, Alastair G; McRobert, I; Ward, J; Keywood, Melita D; Harnwell, J; et al. (Geophysical Research Letters, 2018)
A likely important feature of the poorly understood aerosol-cloud interactions over the Southern Ocean (SO) is the dominant role of sea spray aerosol, versus terrestrial aerosol. Ice nucleating particles (INPs), or particles required for heterogeneous ice nucleation, present over the SO have not been studied in several decades. In this study, boundary layer aerosol properties and immersion freezing INP number concentrations (nINPs) were measured during a ship campaign that occurred south of Australia (down to 53°S) in March–April 2016. Ocean surface chlorophyll a concentrations ranged from 0.11 to 1.77 mg/m3, and nINPs were a factor of 100 lower than historical surveys, ranging from 0.38 to 4.6 m−3 at −20 °C. The INP population included organic heat-stable material, with contributions from heat-labile material. Lower INP source potentials of SO seawater samples compared to Arctic seawater were consistent with lower ice nucleating site densities in this study compared to north Atlantic air masses.
Keywords: Sørishavet; atmosfæren; iskjerner; iskrystaller; klimatologi; marin organisk aerosol; meteorologi; skyer

Multi-temporal variation of the Ross Sea Polynya in response to climate forcings - Park, Jinku; Kim, Hyun-Cheol; Kidwell, Autumn; Hwang, Jihyun (Polar Research, 2018)
The multi-temporal scales of two physical characteristics (areas and occurrence time) of the Ross Sea Polynya (RSP) in Antarctica were analysed using a sea-ice concentration data set (1979–2014) derived from the Scanning Multichannel Microwave Radiometer, the Special Sensor Microwave Imager and Sensor Microwave Imager Sounder. Then, the Ensemble Empirical Mode Decomposition (EEMD) was applied to the data sets to decompose signals into finite numbers of intrinsic mode functions and a residual mode: long time trend. This approach allowed us to understand the long-term variability of the RSP area and occurrence in response to atmospheric forcing through teleconnections between low and high latitudes by comparing the Nino3.4 and Southern Annular Mode (SAM) indices. The nonlinear trend of the RSP areas derived from the EEMD residual had an upward trending shift in the early 1990s and was fairly consistent with the nonlinear trend of Nino3.4. However, the trend of RSP occurrence time progressively increased and had a significant effect on the long time scale. The trend of the RSP area is significantly correlated (+0.98) with the ratio of the trend of the meridional to zonal wind components related with the nonlinearity of Nino3.4, suggesting that meridional wind stress dominated the changes of the polynya area in the Ross Sea. In addition, the nonlinear trends between the SAM and RSP occurrence time show a strong positive correlation, contributing to the earlier onset of polynya expansion and delayed connection with the open ocean owing to enhanced southerly winds.
Keywords: Sørishavet; havis; klimaendringer; klimatologi; oseanografi; polynja; sjøis; sørlig oscillasjon

Precipitation instruments at Rothera Station, Antarctic Peninsula: a comparative study - Tang, Malcolm S Y; Nettukandy Chenoli, Sheeba; Colwell, Steve; Grant, Rosey; Simms, Mairi; Law, John; Abu Samaha, Azizan (Polar Research, 2018)
Direct measurement of precipitation in the Antarctic using ground-based instruments is important to validate the results from climate models, reanalyses and satellite observations. Quantifying precipitation in Antarctica faces many unique challenges such as wind and other technical difficulties due to the harsh environment. This study compares a variety of precipitation measurements in Antarctica, including satellite data and reanalysis fields at Rothera Station, Antarctica Peninsula. The tipping bucket gauges (TBGs) were less sensitive than laserbased sensors (LBSs). The most sensitive LBS (Visibility and Present Weather Sensor, VPF-730) registered 276 precipitation days, while the most sensitive TBG (Universal Precipitation Gauge, UPG-1000) detected 152 precipitation days. Case studies of the precipitation and seasonal accumulation results show the VPF-730 to be the most reliable precipitation sensor of the evaluated instruments. The precipitation amounts given by the reanalyses were positively correlated with wind speed. The precipitation from the Japanese 55-year Reanalysis was most affected by wind speed. Case studies also show that during low wind periods, precipitation measurements from the instruments were very close to the precipitation measurement given by the Global Precipitation Climatology Project (GPCP) 1-degreedaily (1DD) data. During strong wind events, the GPCP 1DD did not fully capture the effect of wind, accounting for the relatively small precipitation amount. The Laser Precipitation Monitor (LPM) and Campbell Scientific-700 (CS700H) experienced instrumental errors during the study, which caused the precipitation readings to become exceedingly high and low, respectively. Installing multiple LBSs in different locations (in close proximity) can help identify inconsistency in the readings.
Keywords: Antarktis; analyser; klimatologi; meteorologi; nedbør; satellitt observasjoner

Global Cooling Contributed to the Establishment of a Modern-Like East Asian Monsoon Climate by the Early Miocene - Zhang, Ran; Zhang, Zhongshi; Jiang, Dabang (Geophysical Research Letters, 2018)
The establishment of a modern-like monsoon climate in East Asia by the early Miocene was a complex process forced by several factors, and previous studies paid less attention to global cooling. Here we investigate this process using climate modeling by considering changes in topography and global cooling under the early Miocene boundary conditions. Using early Miocene paleogeography and an atmospheric CO2 concentration of 560 ppmv, our model results indicate that a nonzonal climate pattern has appeared in East China but that this climate exhibits weak precipitation and wind seasonality. Such seasonality strengthens as the concentration of atmospheric CO2 decreases from 560 to 420 ppmv and resembles the modern-like condition after the growth of the Antarctic ice sheet. Although the development of East Asian topography can further strengthen this seasonality, our results indicate that global cooling is also pivotal for the establishment of a modern-like monsoon climate in East Asia.
Keywords: Antarktis; innlandsis; klimamodeller; klimatologi; nedbør; paleogeografi

On the effect of topography and wind on warm water inflow—An idealized study of the southern Weddell Sea continental shelf system - Daae, Kjersti; Hattermann, Tore; Darelius, Elin; Fer, Ilker (Journal of Geophysical Research: Oceans, 2017)
An idealized eddy-resolving numerical model, with topographic features common to the southern Weddell Sea, is constructed to study mechanisms through which warm deep water enters a wide continental shelf with a trough. The open ocean, represented by a 1700 m deep channel, is connected to a 400 m deep shelf with a continental slope. The shelf is narrow (50 km) in the east but widens to 300 km at the center of the model domain. Over the narrow shelf, the slope front is balanced by wind-driven Ekman downwelling and counteracting eddy overturning, favoring on-shelf transport of warm water in summer scenarios when fresher surface water is present. Over the wide shelf, the Ekman downwelling ceases, and the mesoscale eddies relax the front. Inflow of warm water is sensitive to along-shelf salinity gradients and is most efficient when denser water over the wide shelf favors up-slope eddy transport along isopycnals of the V-shaped slope front. Inflow along the eastern side of the trough cannot penetrate the sill region due to potential vorticity constraints, while along the western trough flank, eddy-induced inflow crosses the sill and reaches the ice front. The warm inflow into the trough is sensitive to the density of the outflowing dense shelf water. For weaker winds, absence of the dense water outflow leads to a reversal of the trough circulation and a strong inflow of warm water, while for stronger winds, baroclinic effects become less important and the inflow is similar to experiments including dense water outflow.
Keywords: Sørishavet; Weddellhavet; batymetri; geofysikk; havstrømmer; hydrografi; klimamodeller; klimatologi; kontinentalsokkel; vannvirvler

A global ocean climatology of preindustrial and modern ocean δ13C - Eide, Marie; Olsen, Are; Ninnemann, Ulysses S; Johannessen, Truls (Global Biogeochemical Cycles, 2017)
We present a global ocean climatology of dissolved inorganic carbon δ13C (‰) corrected for the 13C-Suess effect, preindustrial δ13C. This was constructed by first using Olsen and Ninnemann's (2010) back-calculation method on data from 25 World Ocean Circulation Experiment cruises to reconstruct the preindustrial δ13C on sections spanning all major oceans. Next, we developed five multilinear regression equations, one for each major ocean basin, which were applied on the World Ocean Atlas data to construct the climatology. This reveals the natural δ13C distribution in the global ocean. Compared to the modern distribution, the preindustrial δ13C spans a larger range of values. The maxima, of up to 1.8‰, occurs in the subtropical gyres of all basins, in the upper and intermediate waters of the North Atlantic, as well as in mode waters with a Southern Ocean origin. Particularly strong gradients occur at intermediate depths, revealing a strong potential for using δ13C as a tracer for changes in water mass geometry at these levels. Further, we identify a much tighter relationship between δ13C and apparent oxygen utilization (AOU) than between δ13C and phosphate. This arises because, in contrast to phosphate, AOU and δ13C are both partly reset when waters are ventilated in the Southern Ocean and underscore that δ13C is a highly robust proxy for past changes in ocean oxygen content and ocean ventilation. Our global preindustrial δ13C climatology is openly accessible and can be used, for example, for improved model evaluation and interpretation of sediment δ13C records.
Keywords: Sørishavet; klimatologi; uorganisk karbon; vannmasser

Oceanographic Controls on the Variability of Ice-Shelf Basal Melting and Circulation of Glacial Meltwater in the Amundsen Sea Embayment, Antarctica - Kimura, Satoshi; Jenkins, Adrian; Regan, Heather; Holland, Paul R; Assmann, Karen M; Whitt, Daniel B; Van Wessem, Melchoir; van de Berg, Willem Jan; Reijmer, Carleen H; Dutrieux, Pierre (Journal of Geophysical Research: Oceans, 2017)
Ice shelves in the Amundsen Sea Embayment have thinned, accelerating the seaward flow of ice sheets upstream over recent decades. This imbalance is caused by an increase in the ocean-driven melting of the ice shelves. Observations and models show that the ocean heat content reaching the ice shelves is sensitive to the depth of thermocline, which separates the cool, fresh surface waters from warm, salty waters. Yet the processes controlling the variability of thermocline depth remain poorly constrained. Here we quantify the oceanic conditions and ocean-driven melting of Cosgrove, Pine Island Glacier (PIG), Thwaites, Crosson, and Dotson ice shelves in the Amundsen Sea Embayment from 1991 to 2014 using a general circulation model. Ice-shelf melting is coupled to variability in the wind field and the sea-ice motions over the continental shelf break and associated onshore advection of warm waters in deep troughs. The layer of warm, salty waters at the calving front of PIG and Thwaites is thicker in austral spring (June–October) than in austral summer (December–March), whereas the seasonal cycle at the calving front of Dotson is reversed. Furthermore, the ocean-driven melting in PIG is enhanced by an asymmetric response to changes in ocean heat transport anomalies at the continental shelf break: melting responds more rapidly to increases in ocean heat transport than to decreases. This asymmetry is caused by the inland deepening of bathymetry and the glacial meltwater circulation around the ice shelf.
Keywords: Amundsenhavet; Sørishavet; batymetri; brehylle; glasiologi; isbrem; ismeltvann; isshelf; klimatologi; oseanografi

Autonomous observing platform CO2 data shed new light on the Southern Ocean carbon cycle - Olsen, Are (Global Biogeochemical Cycles, 2017)
While the number of surface ocean CO2 partial pressure (pCO2) measurements has soared the recent decades, the Southern Ocean remains undersampled. Williams et al. (2017, https://doi.org/10.1002/2016GB005541) now present pCO2 estimates based on data from pH-sensor equipped Bio-Argo floats, which have been measuring in the Southern Ocean since 2014. The authors demonstrate the utility of these data for understanding the carbon cycle in this region, which has a large influence on the distribution of CO2 between the ocean and atmosphere. Biogeochemical sensors deployed on autonomous platforms hold the potential to shape our view of the ocean carbon cycle in the coming decades.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; kartlegging; klimaendringer; klimatologi; observasjoner

Observation-Based Trends of the Southern Ocean Carbon Sink - Ritter, Rebecca; Landschützer, Peter; Gruber, Nicolas; Fay, Amanda R; Iida, Yosuke; Jones, Stephen Daniel; Nakaoka, Shin-ichiro; Park, Geun-Ha; Peylin, Philippe; Rödenbeck, Christian; Rodgers, Keith B; Shutler, Jamie D; et al. (Geophysical Research Letters, 2017)
The Southern Ocean (SO) carbon sink has strengthened substantially since the year 2000, following a decade of a weakening trend. However, the surface ocean pCO2 data underlying this trend reversal are sparse, requiring a substantial amount of extrapolation to map the data. Here we use nine different pCO2 mapping products to investigate the SO trends and their sensitivity to the mapping procedure. We find a robust temporal coherence for the entire SO, with eight of the nine products agreeing on the sign of the decadal trends, that is, a weakening CO2 sink trend in the 1990s (on average 0.22 ± 0.24 Pg C yr−1 decade−1), and a strengthening sink trend during the 2000s (−0.35 ± 0.23 Pg C yr−1 decade−1). Spatially, the multiproduct mean reveals rather uniform trends, but the confidence is limited, given the small number of statistically significant trends from the individual products, particularly during the data-sparse 1990–1999 period.
Keywords: Sørishavet; biogeokjemi; global oppvarming; karbondioksid; klimaendringer; klimatologi; meteorologi

Ocean mixing beneath Pine Island Glacier ice shelf, West Antarctica - Kimura, Satoshi; Jenkins, Adrian; Dutrieux, Pierre; Forryan, Alexander; Naveira Garabato, Alberto C; Firing, Yvonne (Journal of Geophysical Research: Oceans, 2016)
Ice shelves around Antarctica are vulnerable to an increase in ocean-driven melting, with the melt rate depending on ocean temperature and the strength of flow inside the ice-shelf cavities. We present measurements of velocity, temperature, salinity, turbulent kinetic energy dissipation rate, and thermal variance dissipation rate beneath Pine Island Glacier ice shelf, West Antarctica. These measurements were obtained by CTD, ADCP, and turbulence sensors mounted on an Autonomous Underwater Vehicle (AUV). The highest turbulent kinetic energy dissipation rate is found near the grounding line. The thermal variance dissipation rate increases closer to the ice-shelf base, with a maximum value found ∼0.5 m away from the ice. The measurements of turbulent kinetic energy dissipation rate near the ice are used to estimate basal melting of the ice shelf. The dissipation-rate-based melt rate estimates is sensitive to the stability correction parameter in the linear approximation of universal function of the Monin-Obukhov similarity theory for stratified boundary layers. We argue that our estimates of basal melting from dissipation rates are within a range of previous estimates of basal melting.
Keywords: Sørishavet; batymetri; brehylle; isbrem; isshelf; klimatologi; målinger; oseanografi; smeltevann; vannmasser

Evaluating CMIP5 ocean biogeochemistry and Southern Ocean carbon uptake using atmospheric potential oxygen: Present-day performance and future projection - Nevison, Cynthia; Manizza, Manfredi; Keeling, Ralph; Stephens, Britton; Bent, Jonathan; Dunne, John P; Ilyina, Tatiana; Long, Matthew; Resplandy, Laure; Tjiputra, Jerry; Yukimoto, Seiji (Geophysical Research Letters, 2016)
Observed seasonal cycles in atmospheric potential oxygen (APO ~ O2 + 1.1 CO2) were used to evaluate eight ocean biogeochemistry models from the Coupled Model Intercomparison Project (CMIP5). Model APO seasonal cycles were computed from the CMIP5 air-sea O2 and CO2 fluxes and compared to observations at three Southern Hemisphere monitoring sites. Four of the models captured either the observed APO seasonal amplitude or phasing relatively well, while the other four did not. Many models had an unrealistic seasonal phasing or amplitude of the CO2 flux, which in turn influenced APO. By 2100 under RCP8.5, the models projected little change in the O2 component of APO but large changes in the seasonality of the CO2 component associated with ocean acidification. The models with poorer performance on present-day APO tended to project larger net carbon uptake in the Southern Ocean, both today and in 2100.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; meteorologi; oseanografi

Pacific-Atlantic Circumpolar Deep Water coupling during the last 500 ka - Ullermann, Johannes; Lamy, Frank; Ninnemann, Ulysses; Lembke-Jene, Lester; Gersonde, Rainer; Tiedemann, Ralf (Paleoceanography, 2016)
Investigating the interbasin deepwater exchange between the Pacific and Atlantic Oceans over glacial-interglacial climate cycles is important for understanding circum-Antarctic Southern Ocean circulation changes and their impact on the global Meridional Overturning Circulation. We use benthic foraminiferal δ13C records from the southern East Pacific Rise to characterize the δ13C composition of Circumpolar Deep Water in the South Pacific, prior to its transit through the Drake Passage into the South Atlantic. A comparison with published South Atlantic deepwater records from the northern Cape Basin suggests a continuous water mass exchange throughout the past 500 ka. Almost identical glacial-interglacial δ13C variations imply a common deepwater evolution in both basins suggesting persistent Circumpolar Deep Water exchange and homogenization. By contrast, deeper abyssal waters occupying the more southern Cape Basin and the southernmost South Atlantic have lower δ13C values during most, but not all, stadial periods. We conclude that these values represent the influence of a more southern water mass, perhaps Antarctic Bottom Water (AABW). During many interglacials and some glacial periods, the gradient between Circumpolar Deep Water and the deeper southern Cape Basin bottom water disappears suggesting either no presence of AABW or indistinguishable δ13C values of both water masses.
Keywords: AABW; Sørishavet; Sørishavsstrømmen; klimatologi; oseanografi; paleoseanografi

Observational evidence of the influence of Antarctic stratospheric ozone variability on middle atmosphere dynamics - Narukull, Venkateswara Rao; Espy, Patrick Joseph; Hibbins, Robert; Fritts, David C; Kavanagh, Andrew John (Geophysical Research Letters, 2015)
Abstract Modeling results have suggested that the circulation of the stratosphere and mesosphere in spring is strongly affected by the perturbations in heating induced by the Antarctic ozone hole. Here using both mesospheric MF radar wind observations from Rothera Antarctica (67°S, 68°W) as well as stratospheric analysis data, we present observational evidence that the stratospheric and mesospheric wind strengths are highly anti-correlated, and show their largest variability in November. We find that these changes are related to the total amount of ozone loss that occurs during the Antarctic spring ozone hole and particularly with the ozone gradients that develop between 57.5°S and 77.5°S. The results show that with increasing ozone loss during spring, winter conditions in the stratosphere and mesosphere persist longer into the summer. These results are discussed in the light of observations of the onset and duration of the Antarctic polar mesospheric cloud season.
Keywords: Antarktis; klimatologi; meteorologi; ozonhull; ozonlaget

Investigating the recent apparent hiatus in surface temperature increases: 2. Comparison of model ensembles to observational estimates - Thorne, Peter; Outten, Stephen; Bethke, Ingo; Seland, Øyvind (Journal of Geophysical Research: Atmospheres, 2015)
To assess published hypotheses surrounding the recent slowdown in surface warming (hiatus), we compare five available global observational surface temperature estimates to two 30-member ensembles from the Norwegian Earth System Model (NorESM). Model ensembles are initialized in 1980 from the transient historical runs and driven with forcings used in the CMIP5 experiments and updated forcings based upon current observational understanding, described in Part 1. The ensembles' surface temperature trends are statistically indistinguishable over 1998–2012 despite differences in the prescribed forcings. There is thus no evidence that forcing errors play a significant role in explaining the hiatus according to NorESM. The observations fall either toward the lower portion of the ensembles or, for some observational estimates and regions, outside. The exception is the Arctic where the observations fall toward the upper ensemble bounds. Observational data set choices can make a large difference to findings of consistency or otherwise. Those NorESM ensemble members that exhibit Nino3.4 Sea Surface Temperature (SST) trends similar to observed also exhibit comparable tropical and to some extent global mean trends, supporting a role for El Nino Southern Oscillation in explaining the hiatus. Several ensemble members capture the marked seasonality observed in Northern Hemisphere midlatitude trends, with cooling in the wintertime and warming in the remaining seasons. Overall, we find that we cannot falsify NorESM as being capable of explaining the observed hiatus behavior. Importantly, this is not equivalent to concluding NorESM could simultaneously capture all important facets of the hiatus. Similar experiments with further, distinct, Earth System Models are required to verify our findings.
Keywords: Antarktis; atmosfæren; fjernmåling; geofysikk; klimaendringer; klimatologi; meteorologi; observasjoner; polarområdene; temperatur

Counteracting the climate effects of volcanic eruptions using short-lived greenhouse gases - Fuglestvedt, Jan S.; Samset, Bjørn H.; Shine, Keith P. (Geophysical Research Letters, 2014)
A large volcanic eruption might constitute a climate emergency, significantly altering global temperature and precipitation for several years. Major future eruptions will occur, but their size or timing cannot be predicted. We show, for the first time, that it may be possible to counteract these climate effects through deliberate emissions of short-lived greenhouse gases, dampening the abrupt impact of an eruption. We estimate an emission pathway countering a hypothetical eruption 3 times the size of Mount Pinatubo in 1991. We use a global climate model to evaluate global and regional responses to the eruption, with and without counteremissions. We then raise practical, financial, and ethical questions related to such a strategy. Unlike the more commonly discussed geoengineering to mitigate warming from long-lived greenhouse gases, designed emissions to counter temporary cooling would not have the disadvantage of needing to be sustained over long periods. Nevertheless, implementation would still face significant challenges.
Keywords: Antarktis; drivhusgasser; global klimamodell; global oppvarming; klimatologi; nedbør; polarområdene; vulkaner

Assessing the potential of calcium-based artificial ocean alkalinization to mitigate rising atmospheric CO2 and ocean acidification - Ilyina, Tatiana; Wolf-Gladrow, Dieter; Munhoven, Guy; Heinze, Christoph (Geophysical Research Letters, 2013)
Enhancement of ocean alkalinity using calcium compounds, e.g., lime has been proposed to mitigate further increase of atmospheric CO2 and ocean acidification due to anthropogenic CO2 emissions. Using a global model, we show that such alkalinization has the potential to preserve pH and the saturation state of carbonate minerals at close to today's values. Effects of alkalinization persist after termination: Atmospheric CO2 and pH do not return to unmitigated levels. Only scenarios in which large amounts of alkalinity (i.e., in a ratio of 2:1 with respect to emitted CO2) are added over large ocean areas can boost oceanic CO2 uptake sufficiently to avoid further ocean acidification on the global scale, thereby elevating some key biogeochemical parameters, e.g., pH significantly above preindustrial levels. Smaller-scale alkalinization could counteract ocean acidification on a subregional or even local scale, e.g., in upwelling systems. The decrease of atmospheric CO2 would then be a small side effect.
Keywords: Sørishavet; biogeokjemi; havalkalisering; klimatologi; meteorologi; modeller

The impact of abrupt suspension of solar radiation management (termination effect) in experiment G2 of the Geoengineering Model Intercomparison Project (GeoMIP) - Jones, Andy; Haywood, Jim M; Alterskjær, Kari; Boucher, Olivier; Cole, Jason N S; Curry, Charles L; Irvine, Peter J; Ji, Duoying; Kravitz, Ben; Egill Kristjánsson, Jón; Moore, John C; Niemeier, Ulrike; et al. (Journal of Geophysical Research: Atmospheres, 2013)
We have examined changes in climate which result from the sudden termination of geoengineering after 50 years of offsetting a 1% per annum increase in CO2 concentrations by a reduction of solar radiation, as simulated by 11 different climate models in experiment G2 of the Geoengineering Model Intercomparison Project. The models agree on a rapid increase in global-mean temperature following termination accompanied by increases in global-mean precipitation rate and decreases in sea-ice cover. There is no agreement on the impact of geoengineering termination on the rate of change of global-mean plant net primary productivity. There is a considerable degree of consensus for the geographical distribution of temperature change following termination, with faster warming at high latitudes and over land. There is also considerable agreement regarding the distribution of reductions in Arctic sea-ice, but less so for the Antarctic. There is much less agreement regarding the patterns of change in precipitation and net primary productivity, with a greater degree of consensus at higher latitudes.
Keywords: Antarktis; global oppvarming; karbondioksid; klimaendringer; klimamodeller; klimatologi; polarområdene; solstråling

Recent snowfall anomalies in Dronning Maud Land, East Antarctica, in a historical and future climate perspective - Lenaerts, Jan T M; van Meijgaard, Erik; van den Broeke, Michiel R; Ligtenberg, Stefan R M; Horwath, Martin; Isaksson, Elisabeth (Geophysical Research Letters, 2013)
Enhanced snowfall on the East Antarctic ice sheet is projected to significantly mitigate 21st century global sea level rise. In recent years (2009 and 2011), regionally extreme snowfall anomalies in Dronning Maud Land, in the Atlantic sector of East Antarctica, have been observed. It has been unclear, however, whether these anomalies can be ascribed to natural decadal variability, or whether they could signal the beginning of a long-term increase of snowfall. Here we use output of a regional atmospheric climate model, evaluated with available firn core records and gravimetry observations, and show that such episodes had not been seen previously in the satellite climate data era (1979). Comparisons with historical data that originate from firn cores, one with records extending back to the 18th century, confirm that accumulation anomalies of this scale have not occurred in the past ~60 years, although comparable anomalies are found further back in time. We examined several regional climate model projections, describing various warming scenarios into the 21st century. Anomalies with magnitudes similar to the recently observed ones were not present in the model output for the current climate, but were found increasingly probable toward the end of the 21st century.
Keywords: Dronning Maud Land; glasiologi; global oppvarming; havnivåstigning; innlandsis; klimaendringer; klimatologi

Arctic and Antarctic sea ice acts as a sink for atmospheric CO2 during periods of snowmelt and surface flooding - Nomura, Daiki; Granskog, Mats A; Assmy, Philipp; Simizu, Daisuke; Hashida, Gen (Journal of Geophysical Research: Oceans, 2013)
In this study, we present evidence that Antarctic and Arctic sea ice act as sink for atmospheric CO2 during periods of snowmelt and surface flooding. The CO2 flux measured directly at the flooded sea ice surface (Fflood) constituted a net CO2 sink of −1.1 ± 0.9 mmol C m−2 d−1 (mean ± 1 SD), which was an order of magnitude higher than the flux measured at the snow-air surface (Fsnow) and bare ice surface (Fice). The Fsnow/Fflood ratio decreased with increasing water equivalent of snow and superimposed-ice, suggesting that the properties of snow and superimposed-ice formation affect the magnitude of the CO2 flux. The Fsnow/Fflood ratio ranged from 0.1 to 0.5, illustrating that 50–90% of the potential flux at the flooded surface was reduced due to the presence of snow/superimposed-ice. Hence, snow cover properties and superimposed-ice play an important role in the CO2 fluxes across the sea ice-snow-atmosphere interface.
Keywords: Sørishavet; atmosfæren; gassutveksling; havis; karbondioksid; klimaendringer; klimatologi; meteorologi; polarområdene; sjøis

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Observed variations in multidecadal Antarctic sea ice trends during 1979–2012 - Simpkins, Graham R; Ciasto, Laura M; England, Matthew H (Geophysical Research Letters, 2013)
The spatiotemporal sensitivity of Antarctic sea ice season length trends are examined using satellite-derived observations over 1979–2012. While the large-scale spatial structure of multidecadal trends has varied little during the satellite record, the magnitude of trends has undergone substantial weakening over the past decade. This weakening is particularly evident in the Ross and Bellingshausen Seas, where a ∼25–50% reduction is observed when comparing trends calculated over 1979–2012 and 1979–1999. Multidecadal trends in the Bellingshausen Sea are found to be dominated by variability over subdecadal time scales, particularly the rapid decline in season length observed between 1979 and 1989. In fact, virtually no trend is detectable when the first decade is excluded from trend calculations. In contrast, the sea ice expansion in the Ross Sea is less influenced by shorter-term variability, with trends shown to be more consistent at decadal time scales and beyond. Understanding these contrasting characteristics have implications for sea ice trend attribution.
Keywords: Sørishavet; havis; klimatologi; observasjoner; satellite bilder; sjøis

Surface mass balance on Fimbul ice shelf, East Antarctica: Comparison of field measurements and large-scale studies - Sinisalo, Anna; Anschütz, Helgard; Aasen, Anne Tårånd; Langley, Kirsty; von Deschwanden, Angela; Kohler, Jack; Matsuoka, Kenichi; Hamran, Svein- Erik; Øyan, Mats-Jørgen; Schlosser, Elisabeth; Hagen, Jon Ove; Nøst, Ole Anders; et al. (Journal of Geophysical Research: Atmospheres, 2013)
Many challenges remain for estimating the Antarctic ice sheet surface mass balance (SMB), which represents a major uncertainty in predictions of future sea-level rise. Validating continental scale studies is hampered by the sparse distribution of in situ data. Here we present a 26 year mean SMB of the Fimbul ice shelf in East Antarctica between 1983–2009, and recent interannual variability since 2010. We compare these data to the results of large-scale SMB studies for similar time periods, obtained from regional atmospheric modeling and remote sensing. Our in situ data include ground penetrating radar, firn cores, and mass balance stakes and provide information on both temporal and spatial scales. The 26 year mean SMB on the Fimbul ice shelf varies between 170 and 620 kg m−2 a−1 giving a regional average value of 310 ± 70 kg m−2 a−1. Our measurements indicate higher long-term accumulation over large parts of the ice shelf compared to the large-scale studies. We also show that the variability of the mean annual SMB, which can be up to 90%, can be a dominant factor in short-term estimates. The results emphasize the importance of using a combination of ground-based validation data, regional climate models, and remote sensing over a relevant time period in order to achieve a reliable SMB for Antarctica.
Keywords: Dronning Maud Land; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi

Can we use ice sheet reconstructions to constrain meltwater for deglacial simulations? - Bethke, Ingo; Li, Camille; Nisancioglu, Kerim H (Paleoceanography, 2012)
Freshwater pulses from melting ice sheets are thought to be important for driving deglacial climate variability. This study investigates challenges in simulating and understanding deglacial climate evolution within this framework, with emphasis on uncertainties in the ocean overturning sensitivity to meltwater inputs. The response of an intermediate complexity model to a single Northern Hemisphere meltwater pulse is familiar: a weakening of the ocean overturning circulation in conjunction with an expansion of sea ice cover and a meridional temperature seesaw. Nonlinear processes are vital in shaping this response and are found to have a decisive influence when more complex scenarios with a history of pulses are involved. A meltwater history for the last deglaciation (21–9 ka) was computed from the ICE-5G ice sheet reconstruction, and the meltwater was routed into the ocean through idealized ice sheet drainages. Forced with this meltwater history, model configurations with altered freshwater sensitivity produce a range of outcomes for the deglaciation, from those in which there is a complete collapse of the overturning circulation to those in which the overturning circulation weakens slightly. The different outcomes are interpreted in terms of the changing hysteresis behavior of the overturning circulation (i.e., non-stationary freshwater sensitivity) as the background climate warms through the course of the deglaciation. The study illustrates that current uncertainties in model sensitivity are limiting in efforts to forward-model deglacial climate variability. Furthermore, ice sheet reconstructions are shown to provide poor constraints on meltwater forcing for simulating the deglaciation.
Keywords: Sørishavet; global oppvarming; havnivåstigning; innlandsis; isavsmelting; klimamodeller; klimatologi; polarområdene; smeltevann

Deciphering the role of southern gateways and carbon dioxide on the onset of the Antarctic Circumpolar Current - Lefebvre, Vincent; Donnadieu, Yannick; Sepulchre, Pierre; Swingedouw, Didier; Zhang, Zhong-Shi (Paleoceanography, 2012)
Growth of Antarctic ice sheet during the Cenozoic 34 million years ago appears as a potential tipping point in the long term cooling trend that began 50 Ma ago. For decades, the onset of the Antarctic Circumpolar Current (ACC) following the opening of the Drake Passage and of the Tasman Seaway has been suggested as the main driver of the continental-scale Antarctic glaciation. However, recent modeling works emphasized that the Eocene/Oligocene atmospheric carbon dioxide (CO2) lowering could be the primary forcing of the Antarctic glaciation, questioning the ACC theory. Here, we investigate the response of the ACC to changes in CO2concentrations occurring from the late Eocene to the late Oligocene. We used a fully coupled atmosphere-ocean model (FOAM) with a mid-Oligocene geography. We find that the opening of southern oceanic gateways does not trigger the onset of the ACC for CO2typical of the late Eocene (>840 ppm). A cooler background climatic state such as the one prevalent at the end of the Oligocene is required to simulate a well-developed ACC. In this cold configuration, the intensified sea-ice development around Antarctica and the resulting brine formation lead to a strong latitudinal density gradient in the Southern Ocean favoring the compensation of the Ekman transport, and consequently the ACC. Our results imply that the ACC has acted as a feedback rather than as a driver of the global cooling.
Keywords: Sørishavet; Sørishavsstrømmen; havstrømmer; karbondioksid; klimatologi; paleogeografi

Variation of accumulation rates over the last eight centuries on the East Antarctic Plateau derived from volcanic signals in ice cores - Anschütz, Helgard; Sinisalo, Anna; Isaksson, Elisabeth; McConnell, Joseph R; Hamran, Svein Erik; Bisiaux, M M; Pasteris, Daniel R; Neumann, Thomas; Winther, Jan-Gunnar (Journal of Geophysical Research: Atmospheres, 2011)
Volcanic signatures in ice-core records provide an excellent means to date the cores and obtain information about accumulation rates. From several ice cores it is thus possible to extract a spatio-temporal accumulation pattern. We show records of electrical conductivity and sulfur from 13 firn cores from the Norwegian-USA scientific traverse during the International Polar Year 2007–2009 (IPY) through East Antarctica. Major volcanic eruptions are identified and used to assess century-scale accumulation changes. The largest changes seem to occur in the most recent decades with accumulation over the period 1963–2007/08 being up to 25% different from the long-term record. There is no clear overall trend, some sites show an increase in accumulation over the period 1963 to present while others show a decrease. Almost all of the sites above 3200 m above sea level (asl) suggest a decrease. These sites also show a significantly lower accumulation value than large-scale assessments both for the period 1963 to present and for the long-term mean at the respective drill sites. The spatial accumulation distribution is influenced mainly by elevation and distance to the ocean (continentality), as expected. Ground-penetrating radar data around the drill sites show a spatial variability within 10–20% over several tens of kilometers, indicating that our drill sites are well representative for the area around them. Our results are important for large-scale assessments of Antarctic mass balance and model validation.
Keywords: Antarktis; akkumulasjon; geovitenskap; glasiologi; innlandsis; iskjerner; klimatologi

A comparison of the present and last interglacial periods in six Antarctic ice cores - Masson-Delmotte, Valerie; Buiron, Daphné; Ekaykin, Alexey Anatolievich; Frezzotti, M; Gallée, Hubert; Jouzel, Jean; Krinner, Gerhard; Landais, Amaelle; Motoyama, Hideaki; Oerter, Hans; Pol, K; Pollard, D; et al. (Clim. Past, 2011)
We compare the present and last interglacial periods as recorded in Antarctic water stable isotope records now available at various temporal resolutions from six East Antarctic ice cores: Vostok, Taylor Dome, EPICA Dome C (EDC), EPICA Dronning Maud Land (EDML), Dome Fuji and the recent TALDICE ice core from Talos Dome. We first review the different modern site characteristics in terms of ice flow, meteorological conditions, precipitation intermittency and moisture origin, as depicted by meteorological data, atmospheric reanalyses and Lagrangian moisture source diagnostics. These different factors can indeed alter the relationships between temperature and water stable isotopes. Using five records with sufficient resolution on the EDC3 age scale, common features are quantified through principal component analyses. Consistent with instrumental records and atmospheric model results, the ice core data depict rather coherent and homogenous patterns in East Antarctica during the last two interglacials. Across the East Antarctic plateau, regional differences, with respect to the common East Antarctic signal, appear to have similar patterns during the current and last interglacials. We identify two abrupt shifts in isotopic records during the glacial inception at TALDICE and EDML, likely caused by regional sea ice expansion. These regional differences are discussed in terms of moisture origin and in terms of past changes in local elevation histories, which are compared to ice sheet model results. Our results suggest that elevation changes may contribute significantly to inter-site differences. These elevation changes may be underestimated by current ice sheet models.
Keywords: Antarktis; Dronning Maud Land; Sørishavet; atmosfæren; glasiologi; iskjerner; klimatologi; meteorologi; stabile isotoper

Atmospheric histories and global emissions of the anthropogenic hydrofluorocarbons HFC-365mfc, HFC-245fa, HFC-227ea, and HFC-236fa - Vollmer, Martin K; Miller, Benjamin R; Rigby, Matthew; Reimann, Stefan; Mühle, Jens; Krummel, Paul B; O'Doherty, Simon; Kim, Jooil; Rhee, Tae Siek; Weiss, Ray F; Fraser, Paul J; Simmonds, Peter G; et al. (Journal of Geophysical Research: Atmospheres, 2011)
We report on ground-based atmospheric measurements and emission estimates of the four anthropogenic hydrofluorocarbons (HFCs) HFC-365mfc (CH3CF2CH2CF3, 1,1,1,3,3-pentafluorobutane), HFC-245fa (CHF2CH2CF3, 1,1,1,3,3-pentafluoropropane), HFC-227ea (CF3CHFCF3, 1,1,1,2,3,3,3-heptafluoropropane), and HFC-236fa (CF3CH2CF3, 1,1,1,3,3,3-hexafluoropropane). In situ measurements are from the global monitoring sites of the Advanced Global Atmospheric Gases Experiment (AGAGE), the System for Observations of Halogenated Greenhouse Gases in Europe (SOGE), and Gosan (South Korea). We include the first halocarbon flask sample measurements from the Antarctic research stations King Sejong and Troll. We also present measurements of archived air samples from both hemispheres back to the 1970s. We use a two-dimensional atmospheric transport model to simulate global atmospheric abundances and to estimate global emissions. HFC-365mfc and HFC-245fa first appeared in the atmosphere only ∼1 decade ago; they have grown rapidly to globally averaged dry air mole fractions of 0.53 ppt (in parts per trillion, 10−12) and 1.1 ppt, respectively, by the end of 2010. In contrast, HFC-227ea first appeared in the global atmosphere in the 1980s and has since grown to ∼0.58 ppt. We report the first measurements of HFC-236fa in the atmosphere. This long-lived compound was present in the atmosphere at only 0.074 ppt in 2010. All four substances exhibit yearly growth rates of >8% yr−1 at the end of 2010. We find rapidly increasing emissions for the foam-blowing compounds HFC-365mfc and HFC-245fa starting in ∼2002. After peaking in 2006 (HFC-365mfc: 3.2 kt yr−1, HFC-245fa: 6.5 kt yr−1), emissions began to decline. Our results for these two compounds suggest that recent estimates from long-term projections (to the late 21st century) have strongly overestimated emissions for the early years of the projections (∼2005–2010). Global HFC-227ea and HFC-236fa emissions have grown to average values of 2.4 kt yr−1 and 0.18 kt yr−1 over the 2008–2010 period, respectively.
Keywords: Dronning Maud Land; atmosfæren; drivhusgasser; global oppvarming; klimaendringer; klimatologi; målinger

An inter-comparison of six latent and sensible heat flux products over the Southern Ocean - Yu, Lejiang; Zhang, Zhanhai; Zhong, Shiyuan; Zhou, Mingyu; Gao, Zhiqiu; Wu, Huiding; Sun, Bo (Polar Research, 2011)
The latent heat fluxes (LHF) and sensible heat fluxes (SHF) over the Southern Ocean from six different data sets are inter-compared for the period 1988- 2000. The six data sets include three satellite-based products, namely, the second version of the Goddard Satellite-Based Surface Turbulent Fluxes data set (GSSTF-2), the third version of the Hamburg Ocean Atmosphere Parameters and Fluxes from Satellite Data (HOAPS-3) and the Japanese Ocean Fluxes Data Sets with Use of Remote Sensing Observations (J-OFURO); two global reanalysis products, namely, the National Centers for Environmental Prediction-Department of Energy Reanalysis 2 data set (NCEP-2) and the European Centre for Medium-Range Weather Forecasts 40 Year Re-analysis data set (ERA-40); and the Objectively Analyzed Air-Sea Fluxes for the Global Oceans data set (OAFlux). All these products reveal a similar pattern in the averaged flux fields. The zonal mean LHF fields all exhibit a continuous increase equatorward. With an exception of HOAPS-3, the zonal mean SHF fields display a minimum value near 50°S, increasing both pole- and equatorward. The differences in the standard deviation for LHF are larger among the six data products than the differences for SHF. Over the regions where the surface fluxes are significantly influenced by the Antarctic Oscillation and the Pacific-South American teleconnection, the values and distributions of both LHF and SHF are consistent among the six products. It was found that the spatial patterns of the standard deviations and trends of LHF and SHF can be explained primarily by sea-air specific humidity and temperature differences; wind speed plays a minor role. Keywords: Latent heat flux; sensible heat flux; Southern Ocean.
Keywords: Sørishavet; klimatologi; meteorologi; observasjoner

Antarctic clouds - Lachlan-Cope, Tom (Polar Research, 2010)
Sensitivity studies with global climate models show that, by their influence on the radiation balance, Antarctic clouds play a major role in the climate system, both directly at high southern latitudes and indirectly globally, as the local circulation changes lead to global teleconnections. Unfortunately, observations of cloud distribution in the Antarctic are limited and often of low quality because of the practical difficulty in observing clouds in the harsh Antarctic environment. The best surface observations suggest that the fractional cloud cover at the South Pole is around 50–60% in all seasons, whereas the cloud cover rises to around 80–90% close to the coast of the continent. Microphysical observations of cloud parameters are also very sparse in the Antarctic. However, the few measurements that do exist show predominantly ice-crystal clouds across the interior, with mixed-phase clouds close to the coasts. Crystal sizes vary from 5 to 30 mm (effective radius) in the interior to somewhat larger ice crystals and water drops near the coast. A wide range of crystal shapes is observed at all sites. This review considers the available cloud observations and highlights the importance of Antarctic clouds and the need for better observations in the future.
Keywords: Antarktis; klimatologi; meteorologi; observasjoner; satellitt bilder; skyer

An extreme precipitation event in Dronning Maud Land, Antarctica: a case study with the Antarctic Mesoscale Prediction System - Schlosser, Elisabeth; Powers, Jordan G.; Duda, Michael G.; Manning, Kevin W.; Reijmer, Carleen H.; van den Broeke, Michiel R. (Polar Research, 2010)
An extreme precipitation event that influenced almost the whole polar plateau of Dronning Maud Land, Antarctica, is investigated using Antarctic Mesoscale Prediction System archive data. For the first time a high-resolution atmospheric model especially adapted for polar regions was used for such a study in Dronning Maud Land. The outstanding event of 21–25 February 2003 was connected to a strong north-westerly flow, caused by a blocking high above eastern Dronning Maud Land, that persisted for several days and brought unusually large levels of moisture to the Antarctic Plateau. This weather situation is most effective in bringing precipitation to high-altitude interior Antarctic ice-core drilling sites, where precipitation in the form of diamond dust usually dominates. However, a few such precipitation events per year can account for a large percentage of the annual accumulation, which can cause a strong bias in ice-core data. Additionally, increased temperatures and wind speeds during these events need to be taken into account for the correct climatic interpretation of ice cores. A better understanding of the frequency of occurrence of intermittent precipitation in the interior of Antarctica in past and future climates is necessary for both palaeoclimatological studies and estimates of future sea-level change.
Keywords: Dronning Maud Land; havnivåstigning; klimaendringer; klimatologi; meteorologi; nedbør; polarområdene

Characteristics of atmospheric transport into the Antarctic troposphere - Stohl, Andreas; Sodemann, Harald (Journal of Geophysical Research: Atmospheres, 2010)
We have developed a 5.5 year climatology of atmospheric transport into the Antarctic troposphere, which uses the same data set and methods as described in a recent study for the Arctic. This allows direct comparisons of transport properties for the two polar regions. The climatology is based on a simulation with the Lagrangian particle dispersion model FLEXPART, where the model atmosphere was globally filled with particles. Transport characteristics as well as emission sensitivities were derived from 6 hourly particle positions. We found that the probability for near-surface air to originate from the stratosphere on a time scale of 10 days is an order of magnitude higher near the South Pole than near the North Pole, a result of higher topography and descent that partly compensates for the flow of air down the Antarctic Plateau with the katabatic winds. The stratospheric influence is largest in fall, which is opposite to the seasonality in the Arctic. Stratospheric influence is much smaller over the shelf ice regions and in a band around Antarctica. The average time for which air near the surface has been exposed to continuous darkness in July (continuous light in January) is longest over the Ronne Ice Shelf and Ross Ice Shelf at ∼11 days (20 days). We calculated how sensitive Antarctic air masses are to emission input up to 30 days before arriving in Antarctica if removal processes are ignored. The emission sensitivity shows strong meridional gradients and, as a result, is generally low over South America, Africa, and Australia. For a 10 day time scale, the largest emission sensitivities over these continents are 1–2 orders of magnitude smaller than over Eurasia for transport to the Arctic, showing that foreign continents have a much smaller potential to pollute the Antarctic than the Arctic troposphere. Emission sensitivities and derived black carbon (BC) source contributions over South America, Africa, and Australia are substantially (a factor 10 for Africa) larger in winter than in summer. In winter, biomass burning contributes more BC than anthropogenic sources. For typical aerosol lifetimes of 5–10 days, ship emissions south of 60°S account for half of the total BC concentrations in the lowest 1000 m of the atmosphere south of 70°S in December. The increasing number of tourists visiting Antarctica and fishing vessels operating close to Antarctica are, therefore, a matter of concern.
Keywords: Antarktis; cruiseturisme; forurensning; klimatologi; polarområdene; stratosfæren; utslipp

Tracing biomass burning aerosol from South America to Troll Research Station, Antarctica - Fiebig, Markus; Lunder, Chris René; Stohl, Andreas (Geophysical Research Letters, 2009)
The atmospheric observatory at the Norwegian Research Station Troll in Queen Maud Land, Antarctica, holds, since February 2007, the first all-year Antarctic atmospheric aerosol particle number size distribution measurements. These are colocated with measurements of the aerosol absorption and spectral scattering coefficients. In June 2007, this instrument set observed an aerosol whose properties were indicative of a biomass burning aerosol. These properties included two log-normal size distribution modes with median particle diameters of 0.105 μm and 0.36 μm, sharply falling off to smaller and larger sizes, and peaks in scattering and absorption coefficient. With backward plume calculations of the Lagrangian transport model FLEXPART and the MODIS fire activity product, a source-receptor relationship was established between biomass burning events in Central Brazil and the aerosol seen at Troll. This is the first direct evidence that the Antarctic continent is susceptible to emissions from as far north as Southern tropical latitudes.
Keywords: Dronning Maud Land; Troll forskningsstasjon; biomasse; klimatologi; meteorologi; utslipp

Evolution of first-year and second-year snow properties on sea ice in the Weddell Sea during spring-summer transition - Nicolaus, Marcel; Haas, Christian; Willmes, Sascha (Journal of Geophysical Research: Atmospheres, 2009)
Observations of snow properties, superimposed ice, and atmospheric heat fluxes have been performed on first-year and second-year sea ice in the western Weddell Sea, Antarctica. Snow in this region is particular as it does usually survive summer ablation. Measurements were performed during Ice Station Polarstern (ISPOL), a 5-week drift station of the German icebreaker RV Polarstern. Net heat flux to the snowpack was 8 W m−2, causing only 0.1 to 0.2 m of thinning of both snow cover types, thinner first-year and thicker second-year snow. Snow thinning was dominated by compaction and evaporation, whereas melt was of minor importance and occurred only internally at or close to the surface. Characteristic differences between snow on first-year and second-year ice were found in snow thickness, temperature, and stratigraphy. Snow on second-year ice was thicker, colder, denser, and more layered than on first-year ice. Metamorphism and ablation, and thus mass balance, were similar between both regimes, because they depend more on surface heat fluxes and less on underground properties. Ice freeboard was mostly negative, but flooding occurred mainly on first-year ice. Snow and ice interface temperature did not reach the melting point during the observation period. Nevertheless, formation of discontinuous superimposed ice was observed. Color tracer experiments suggest considerable meltwater percolation within the snow, despite below-melting temperatures of lower layers. Strong meridional gradients of snow and sea-ice properties were found in this region. They suggest similar gradients in atmospheric and oceanographic conditions and implicate their importance for melt processes and the location of the summer ice edge.
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; klimatologi; meteorologi; målinger; oseanografi; sjøis; snø; økosystemer

Impacts of the Oceans on Climate Change - Reid, Philip C; Fischer, Astrid C; Lewis-Brown, Emily; Meredith, Michael P; Sparrow, Mike; Andersson, Andreas J; Antia, Avan; Bates, Nicholas R; Bathmann, Ulrich; Beaugrand, Gregory; Brix, Holger; Dye, Stephen; et al. (Advances in Marine Biology, 2009)
The oceans play a key role in climate regulation especially in part buffering (neutralising) the effects of increasing levels of greenhouse gases in the atmosphere and rising global temperatures. This chapter examines how the regulatory processes performed by the oceans alter as a response to climate change and assesses the extent to which positive feedbacks from the ocean may exacerbate climate change. There is clear evidence for rapid change in the oceans. As the main heat store for the world there has been an accelerating change in sea temperatures over the last few decades, which has contributed to rising sea‐level. The oceans are also the main store of carbon dioxide (CO2), and are estimated to have taken up ∼40% of anthropogenic-sourced CO2 from the atmosphere since the beginning of the industrial revolution. A proportion of the carbon uptake is exported via the four ocean ‘carbon pumps’ (Solubility, Biological, Continental Shelf and Carbonate Counter) to the deep ocean reservoir. Increases in sea temperature and changing planktonic systems and ocean currents may lead to a reduction in the uptake of CO2 by the ocean; some evidence suggests a suppression of parts of the marine carbon sink is already underway. While the oceans have buffered climate change through the uptake of CO2 produced by fossil fuel burning this has already had an impact on ocean chemistry through ocean acidification and will continue to do so. Feedbacks to climate change from acidification may result from expected impacts on marine organisms (especially corals and calcareous plankton), ecosystems and biogeochemical cycles. The polar regions of the world are showing the most rapid responses to climate change. As a result of a strong ice–ocean influence, small changes in temperature, salinity and ice cover may trigger large and sudden changes in regional climate with potential downstream feedbacks to the climate of the rest of the world. A warming Arctic Ocean may lead to further releases of the potent greenhouse gas methane from hydrates and permafrost. The Southern Ocean plays a critical role in driving, modifying and regulating global climate change via the carbon cycle and through its impact on adjacent Antarctica. The Antarctic Peninsula has shown some of the most rapid rises in atmospheric and oceanic temperature in the world, with an associated retreat of the majority of glaciers. Parts of the West Antarctic ice sheet are deflating rapidly, very likely due to a change in the flux of oceanic heat to the undersides of the floating ice shelves. The final section on modelling feedbacks from the ocean to climate change identifies limitations and priorities for model development and associated observations. Considering the importance of the oceans to climate change and our limited understanding of climate-related ocean processes, our ability to measure the changes that are taking place are conspicuously inadequate. The chapter highlights the need for a comprehensive, adequately funded and globally extensive ocean observing system to be implemented and sustained as a high priority. Unless feedbacks from the oceans to climate change are adequately included in climate change models, it is possible that the mitigation actions needed to stabilise CO2 and limit temperature rise over the next century will be underestimated.
Keywords: Sørishavet; global oppvarming; havnivåstigning; klimaendringer; klimatologi

Asymmetries in the moisture origin of Antarctic precipitation - Sodemann, Harald; Stohl, Andreas (Geophysical Research Letters, 2009)
The seasonality of moisture sources for precipitation in Antarctica is studied with a Lagrangian moisture source diagnostic. Moisture origin for precipitation in Antarctica has strongly asymmetric properties, which are related to the Antarctic topography, seasonal sea ice coverage, and the land/ocean contrasts in the mid-latitudes of the southern hemisphere. The highest altitudes of the East Antarctic ice shield, where major ice cores have been drilled, have mean source latitudes of 45–40°S year-round. This finding contrasts to results from previous Lagrangian studies which detected a more southerly moisture origin due to too short trajectories. Now, results from Lagrangian moisture source diagnostics are consistent with findings from general circulation models with tagged tracers. Thus, both approaches can serve as a common benchmark for the interpretation of moisture source indicators based on stable isotopes, such as deuterium excess, in Antarctic ice cores.
Keywords: Antarktis; klimatologi; meteorologi; nedbør

Contrasting climate change in the two polar regions - Turner, John; Overland, Jim (Polar Research, 2009)
The two polar regions have experienced remarkably different climatic changes in recent decades. The Arctic has seen a marked reduction in sea-ice extent throughout the year, with a peak during the autumn. A new record minimum extent occurred in 2007, which was 40% below the long-term climatological mean. In contrast, the extent of Antarctic sea ice has increased, with the greatest growth being in the autumn. There has been a large-scale warming across much of the Arctic, with a resultant loss of permafrost and a reduction in snow cover. The bulk of the Antarctic has experienced little change in surface temperature over the last 50 years, although a slight cooling has been evident around the coast of East Antarctica since about 1980, and recent research has pointed to a warming across West Antarctica. The exception is the Antarctic Peninsula, where there has been a winter (summer) season warming on the western (eastern) side. Many of the different changes observed between the two polar regions can be attributed to topographic factors and land/sea distribution. The location of the Arctic Ocean at high latitude, with the consequently high level of solar radiation received in summer, allows the icealbedo feedback mechanism to operate effectively. The Antarctic ozone hole has had a profound effect on the circulations of the high latitude ocean and atmosphere, isolating the continent and increasing the westerly winds over the Southern Ocean, especially during the summer and winter.
Keywords: Antarktis; Sørishavet; havis; klimaendringer; klimatologi; ozonhull; ozonlaget; polarområdene; sjøis

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

How representative is a time series derived from a firn core? A study at a low-accumulation site on the Antarctic plateau - Karlöf, Lars; Winebrenner, Dale P; Percival, Donald B (Journal of Geophysical Research: Earth Surface, 2006)
The acquisition and interpretation of increasingly high-resolution climate data from polar ice and firn cores motivates the question: What is the finest depth or timescale on which measurements on cores arrayed over a given area correlate? We analyze dated depth series of electrical and oxygen isotope measurements from a spatial array of firn cores with 3.5–7 km spacing in Dronning Maud Land, Antarctica, each with a temporal span of approximately 200 years. We use wavelet analysis to decompose the series into components associated with changes of averages on different scales, and thus deduce which scales are dominated by environmental noise, and which may contain a common signal. We find that common signals in electrical records have timescales of approximately 1–3 years. We identify only one electrical signal which rises significantly above the background in our 200-year records, evidently corresponding to the Tambora eruption. Several smaller signals correlate in a few of pairs of cores, one of which may correspond to a known volcanic event, but the others appear to be spurious. We present a simulation-based method for testing the significance of apparent electrical signal correlations, and highlight the importance of accurate relative dating between cores. In the case of oxygen-isotope records, we find, surprisingly, no significant correlation on any scale in the records, for any of the pairs of cores. There is, however, a weak trend toward positive correlation at longer timescales (up to 16 years). Statistical theory for the relevant confidence intervals and the observed statistics of the records permit estimation of the length of a data series necessary to reliably detect a hypothetical correlation equal to that observed. For the highest correlation observed on 16-year scales, core records of about 380 years (approximately 30 m at the Dronning Maud Land site) would be necessary to establish significance.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi; meteorologi; tidsserieanalyse

Ozone profiles in the high-latitude stratosphere and lower mesosphere measured by the Improved Limb Atmospheric Spectrometer (ILAS)-II: Comparison with other satellite sensors and ozonesondes - Sugita, Takafumi; Nakajima, Hideaki; Yokota, T; Kanzawa, Hiroshi; Gernandt, Hartwig; Herber, A; von der Gathen, P; König-Langlo, Gert; Sato, Kaoru; Dorokhov, Valery; Yushkov, V A; Murayama, Yasuhiro; et al. (Journal of Geophysical Research: Atmospheres, 2006)
A solar occultation sensor, the Improved Limb Atmospheric Spectrometer (ILAS)-II, measured 5890 vertical profiles of ozone concentrations in the stratosphere and lower mesosphere and of other species from January to October 2003. The measurement latitude coverage was 54–71°N and 64–88°S, which is similar to the coverage of ILAS (November 1996 to June 1997). One purpose of the ILAS-II measurements was to continue such high-latitude measurements of ozone and its related chemical species in order to help accurately determine their trends. The present paper assesses the quality of ozone data in the version 1.4 retrieval algorithm, through comparisons with results obtained from comprehensive ozonesonde measurements and four satellite-borne solar occultation sensors. In the Northern Hemisphere (NH), the ILAS-II ozone data agree with the other data within ±10% (in terms of the absolute difference divided by its mean value) at altitudes between 11 and 40 km, with the median coincident ILAS-II profiles being systematically up to 10% higher below 20 km and up to 10% lower between 21 and 40 km after screening possible suspicious retrievals. Above 41 km, the negative bias between the NH ILAS-II ozone data and the other data increases with increasing altitude and reaches 30% at 61–65 km. In the Southern Hemisphere, the ILAS-II ozone data agree with the other data within ±10% in the altitude range of 11–60 km, with the median coincident profiles being on average up to 10% higher below 20 km and up to 10% lower above 20 km. Considering the accuracy of the other data used for this comparative study, the version 1.4 ozone data are suitably used for quantitative analyses in the high-latitude stratosphere in both the Northern and Southern Hemisphere and in the lower mesosphere in the Southern Hemisphere.
Keywords: Antarktis; klimatologi; meteorologi; ozonlaget; polarområdene; stratosfæren

Physical properties and stratigraphy of surface snow in western Dronning Maud Land, Antarctica - Kärkäs, Eija; Martma, Tõnu; Sonninen, Eloni (Polar Research, 2005)
Information about the spatial variations of snow properties and of annual accumulation on ice sheets is important if we are to understand the results obtained from ice cores, satellite remote sensing data and changes in climate patterns. The layer structure and spatial variations of physical properties of surface snow in western Dronning Maud Land were analysed during the austral summers 1999/2000, 2000/01 and 2003/04 in fi ve different snow zones. The measurements were performed in shallow (1 - 2 m) snow pits along a transect extending 350 km from the seaward edge of the ice shelf to the polar plateau. These pits covered at least the last annual accumulation and ranged in elevation from near sea level to 2500 m a.s.l. The ?18O values and accumulation rates had a good linear correlation with the distance from the coast. The mean accumulation on the ice shelf was 312 ± 28 mm water equivalent (w.e.); in the coastal region it was 215 ± 43 mm w.e. and on the polar plateau it was 92 ± 25 mm w.e. The mean annual conductivity and grain size values decreased exponentially with increasing distance from the ice edge, by 48 %/100 km and 18 %/100 km respectively. The mean grain size varied between 1.5 and 1.8 mm. Depth hoar layers were a common phenomenon, especially under thin ice crusts, and were associated with low dielectric constant values.
Keywords: Dronning Maud Land; geofysikk; geologi; havnivå; innlandsis; klimatologi; miljøendringer; overflatesnø; snø akkumulasjon; stratigrafi

Accumulation variability over a small area in east Dronning Maud Land, Antarctica, as determined from shallow firn cores and snow pits: some implications for ice-core records - Karlöf, Lars; Isaksson, Elisabeth; Winther, Jan-Gunnar; Gundestrup, Niels; Meijer, Harro A J; Mulvaney, Robert; Pourchet, Michel; Hofstede, Coen; Lappegard, Gaute; Pettersson, Rickard; Van Den Broeke, Michiel; Van De Wal, Roderik S W (Journal of Glaciology, 2005)
We investigate and quantify the variability of snow accumulation rate around a medium-depth firn core (160 m) drilled in east Dronning Maud Land, Antarctica (75°00′ S, 15°00’ E; 3470 m h.a.e. (ellipsoidal height)). We present accumulation data from five snow pits and five shallow (20 m) firn cores distributed within a 3.5–7 km distance, retrieved during the 2000/01 Nordic EPICA (European Project for Ice Coring in Antarctica) traverse. Snow accumulation rates estimated for shorter periods show higher spatial variance than for longer periods. Accumulation variability as recorded from the firn cores and snow pits cannot explain all the variation in the ion and isotope time series; other depositional and post-depositional processes need to be accounted for. Through simple statistical analysis we show that there are differences in sensitivity to these processes between the analyzed species. Oxygen isotopes and sulphate are more conservative in their post-depositional behaviour than the more volatile acids, such as nitrate and to some degree chloride and methanesulphonic acid. We discuss the possible causes for the accumulation variability and the implications for the interpretation of ice-core records.
Keywords: Dronning Maud Land; glasiologi; klimamodeller; klimatologi

The International Trans-Antarctic Scientific Expedition (ITASE): an overview - Mayewski, Paul Andrew; Frezzotti, Massimo; Bertler, Nancy; Ommen, Tas V. A. N.; Hamilton, Gordon; Jacka, Tim H.; Welch, Brian; Frey, Markus; Dahe, Qin; Jiawen, Ren; Simões, Jefferson; Fily, Michel; et al. (Annals of Glaciology, 2005)
From its original formulation in 1990 the International Trans-Antarctic Scientific Expedition (ITASE) has had as its primary aim the collection and interpretation of a continent-wide array of environmental parameters assembled through the coordinated efforts of scientists from several nations. ITASE offers the ground-based opportunities of traditional-style traverse travel coupled with the modern technology of GPS, crevasse detecting radar, satellite communications and multidisciplinary research. By operating predominantly in the mode of an oversnow traverse, ITASE offers scientists the opportunity to experience the dynamic range of the Antarctic environment. ITASE also offers an important interactive venue for research similar to that afforded by oceanographic research vessels and large polar field camps, without the cost of the former or the lack of mobility of the latter. More importantly, the combination of disciplines represented by ITASE provides a unique, multidimensional (space and time) view of the ice sheet and its history. ITASE has now collected >20 000km of snow radar, recovered more than 240 firn/ice cores (total length 7000 m), remotely penetrated to ~4000m into the ice sheet, and sampled the atmosphere to heights of >20 km.
Keywords: Antarktis; Dronning Maud Land; ekspedisjoner; geovitenskap; glasiologi; klimatologi; transantarktiske ekspedisjoner

An Observational Study of the Final Breakdown of the Southern Hemisphere Stratospheric Vortex in 2002 - Orsolini, Yvan J.; Randall, Cora E.; Manney, Gloria L.; Allen, Douglas R. (Journal of the Atmospheric Sciences, 2005)
The 2002 Southern Hemisphere final warming occurred early, following an unusually active winter and the first recorded major warming in the Antarctic. The breakdown of the stratospheric polar vortex in October and November 2002 is examined using new satellite observations from the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) instrument aboard the European Space Agency (ESA) Environment Satellite (ENVISA7-) and meteorological analyses, both high-resolution fields from the European Centre for Medium-Rangc Weather Forecasts and the coarser Met Office analyses. The results derived from MIPAS observations are compared to measurements and inferences from well-validated solar occultation satellite instruments [Halogen Occultation Experiment (HALOE), Polar Ozone and Aerosol Measurement lit (POAM III), and Stratospheric Aerosol and Gas Experiments II and III (SAGE II and III)] and to finescale tracer fields reconstructed by transporting trace gases based oil MIPAS or climatological data using a reverse-trajectory method. These comparisons confirm the features in the MIPAS data and the interpretation of the evolution of the flow during the vortex decay revealed by those features. Mapped ozone and water vapor from MIPAS and the analyzed isentropic potential vorticity vividly display the vortex breakdown, which occurred earlier than usual. A large tongue of vortex air was pulled out westward and coiled up in an anticyclone, while the vortex core remnant shrank and drifted eastward and equatorward over the South Atlantic. By roughly mid-November, the vortex remnant at 10 mb had shrunk below scales resolved by the satellite observations, while a vortex core remained in the lower stratosphere.
Keywords: Antarktis; klimatologi; meteorologi; polarvirvelen; stratosfæren

The effect of diapycnal mixing on the ventilation and CFC-11 uptake in the Southern Ocean - Gao, Yongqi; Drange, Helge (Advances in Atmospheric Sciences, 2004)
The Miami Isopycnic Coordinate Ocean Model (MICOM) is used to investigate the effect of diapycnal mixing on the oceanic uptake of CFC-11 and the ventilation of the surface waters in the Southern Ocean (south of 45°S). Three model experiments are performed: one with a diapycnal mixing coefficientKd (m2 s−1) of 2 × 10−7/N (Expt. 1), one withKd = 0 (Expt. 2), and one withKd = 5 × 10−8/N (Expt. 3),N (s−1) is the Brunt-Väisälä frequency. The model simulations indicate that the observed vertical distribution of CFC-11 along 88°W (prime meridian at 0°E) in the Southern Ocean is caused by local ventilation of the surface waters and westward-directed (eastward-directed) isopycnic transport and mixing from deeply ventilated waters in the Weddell Sea region. It is found that at the end of 1997, the simulated net ocean uptake of CFC-11 in Expt. 2 is 25% below that of Expt. 1. The decreased uptake of CFC-11 in the Southern Ocean accounts for 80% of this difference. Furthermore, Expts. 2 and 3 yield far more realistic vertical distributions of the ventilated CFC-waters than Expt. 1. The experiments clearly highlight the sensitivity of the Southern Ocean surface water ventilation to the distribution and thickness of the simulated mixed layer. It is argued that inclusion of CFCs in coupled climate models could be used as a test-bed for evaluating the decadal-scale ocean uptake of heat and CO2.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; oseanografi; strømmodeller

Accumulation variability derived from an ice core from coastal Dronning Maud Land, Antarctica - Kaczmarska, Marzena; Isaksson, Elisabeth; Karlöf, Lars; Winther, Jan-Gunnar; Kohler, Jack; Godtliebsen, Fred; Olsen, Lena Ringstad; Hofstede, Coen M.; Van Den Broeke, Michiel R.; Van De Wal, Roderik S. W.; Gundestrup, Niels (Annals of Glaciology, 2004)
A 100 m long ice core was retrieved from the coastal area of Dronning Maud Land (DML), Antarctica, in the 2000/01 austral summer. The core was dated to AD 1737 by identification of volcanic horizons in dielectrical profiling and electrical conductivity measurement records in combination with seasonal layer counting from high-resolution oxygen isotope (δ18O) data. A mean long-term accumulation rate of 0.29 ma–1w.e. was derived from the high-resolution δ18O record as well as accumulation rates during periods in between the identified volcanic horizons. A statistically significant decrease in accumulation was found from about 1920 to the present. A comparison with other coastal ice cores from DML suggests that this is a regional pattern.
Keywords: Dronning Maud Land; geofysikk; glasiologi; iskjerner; klimatologi

Description and evaluation of the bergen climate model: ARPEGE coupled with MICOM - Furevik, Tore; Bentsen, Mats; Drange, Helge; Kindem, I. K. T.; Kvamstø, Nils Gunnar; Sorteberg, Asgeir (Climate Dynamics, 2003)
A new coupled atmosphere–ocean–sea ice model has been developed, named the Bergen Climate Model (BCM). It consists of the atmospheric model ARPEGE/IFS, together with a global version of the ocean model MICOM including a dynamic–thermodynamic sea ice model. The coupling between the two models uses the OASIS software package. The new model concept is described, and results from a 300-year control integration is evaluated against observational data. In BCM, both the atmosphere and the ocean components use grids which can be irregular and have non-matching coastlines. Much effort has been put into the development of optimal interpolation schemes between the models, in particular the non-trivial problem of flux conservation in the coastal areas. A flux adjustment technique has been applied to the heat and fresh-water fluxes. There is, however, a weak drift in global mean sea-surface temperature (SST) and sea-surface salinity (SSS) of respectively 0.1 °C and 0.02 psu per century. The model gives a realistic simulation of the radiation balance at the top-of-the-atmosphere, and the net surface fluxes of longwave, shortwave, and turbulent heat fluxes are within observed values. Both global and total zonal means of cloud cover and precipitation are fairly close to observations, and errors are mainly related to the strength and positioning of the Hadley cell. The mean sea-level pressure (SLP) is well simulated, and both the mean state and the interannual standard deviation show realistic features. The SST field is several degrees too cold in the equatorial upwelling area in the Pacific, and about 1 °C too warm along the eastern margins of the oceans, and in the polar regions. The deviation from Levitus salinity is typically 0.1 psu – 0.4 psu, with a tendency for positive anomalies in the Northern Hemisphere, and negative in the Southern Hemisphere. The sea-ice distribution is realistic, but with too thin ice in the Arctic Ocean and too small ice coverage in the Southern Ocean. These model deficiencies have a strong influence on the surface air temperatures in these regions. Horizontal oceanic mass transports are in the lower range of those observed. The strength of the meridional overturning in the Atlantic is 18 Sv. An analysis of the large-scale variability in the model climate reveals realistic El Niño – Southern Oscillation (ENSO) and North Atlantic–Arctic Oscillation (NAO/AO) characteristics in the SLP and surface temperatures, including spatial patterns, frequencies, and strength. While the NAO/AO spectrum is white in SLP and red in temperature, the ENSO spectrum shows an energy maximum near 3 years.
Keywords: Sørishavet; geofysikk; klimamodeller; klimatologi; polarområdene

European project for ice coring in Antarctica (EPICA) - Nordic traverse in 2000/01 - Winther, Jan-Gunnar; Karlöf, Lars; Hofstede, Coen; Johansen, Einar; Johansen, Jan-Tore; De Jong, Eric-Jan; Kaspers, Karsten; Lappegard, Gaute; Pettersson, Rikard; Tronstad, Stein; Van De Wal, Roderik (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; akkumulasjon; atmosfæren; ekspedisjoner; geofysikk; geografi; glasiologi; innlandsis; is radar; iskjerner; klimatologi; meteorologi; snø radar; topografi

Rapid climate shifts in the southern African interior throughout the Mid to Late Holocene - Lee-Thorp, Julia; Holmgren, Karin; Lauritzen, Stein Erik; Linge, Henriette; Moberg, Anders; Partridge, Timothy C; Stevenson, Chris; Tyson Peter D. (Geophysical Research Letters, 2001)
A detailed climate proxy record based on δ18O, δ13O, and grey index of a well-dated stalagmite from Cold Air Cave in the Makapansgat Valley of north-eastern South Africa suggests that regional precipitation, temperatures and vegetation oscillated markedly and rapidly over the last ∼6500 years on centennial and multi-decadal scales. The mid-Holocene prior to 5200 years ago was humid and warm. A fundamental transition occurred 3200 years ago, leading to drier and cooler conditions that culminated at 1750 AD. Comparisons with ice core records suggest synchronous changes implicating rapid global teleconnections.
Keywords: Antarktis; arkeologi; geografi; geologi; klimaendringer; klimatologi; paleontologi

Spatial gradients in snow layering and 10 m temperatures at two EPICA-Dronning Maud Land (Antarctica) pre-site-survey drill sites - Holmlund, P.; Gjerde, K.; Gundestrup, N.; Hansson, M.; Isaksson, E.; Karlöf, L.; Nman, M.; Pettersson, R.; Pinglot, F.; Reijmer, C. H.; Stenberg, M.; Thomassen, M.; et al. (Annals of Glaciology, 2000)
During the 1997/98 field season, Sweden, Norway and The Netherlands performed a pre-site survey for EPICA in Dronning Maud Land, Antarctica. This paper summarizes the results and pays special attention to the high spatial gradients found in snow layering and temperatures. The sites were "Camp Victoria" (CV) on Amundsenisen (76° S, 8° W; 2400 m a.s.l.), approximately 550 km from the coast, and "Camp Maudheimvidda" (CM) on Maudheimvidda (74° S 13° W; 362 m a.s.L), some 140 km from the coast.The drilling programme included both medium-long firn/ice cores and shallow firn cores. These were analysed by means of δ18O, DEP, ECM,β activity, density, and ion content. The combined results suggests a mean annual accumulation rate of 60 mm. we. for CV and 220 mm. we. for CM.Variability measurements of spatial snow layering were performed at two scales; over tens of kilometres by radar and over a few metres by pits and high-resolution radar soundings. Results, as measured by relative standard deviation, were typically 10% on the polar plateau and as high as 50% near the coast.The 10 m temperature measurements were –38.5°C (std dev. = 0.5°) for CV and –17.6°C (std dev.=0.15°) for CM.Snow chemistry was sampled at each medium-long-core drill site. Comparison of δ18O profiles from snow pits and the uppermost part of the CV medium-long core showed large variations. Mean δ18O valuesover 2 m profiles varied between 41.6%, and 39.7%o within a horizontal distance of 50 m.
Keywords: Dronning Maud Land; glasiologi; iskjerner; klimatologi

Effort explores 130 Million years of Antarctic paleoenvironment - Kristoffersen, Yngve; Goodwin, Ian D; Cooper, Alan K (Eos, Transactions American Geophysical Union, 2000)
Antarctic climate history has been dominated by events and turning points with causes that are poorly understood. To fill the gaps in our knowledges new effort is underway in the international geologic community to acquire and coordinate the circum-Antarctic geologic data needed to derive and model paleoenvironments of the past 130 m.y. The effort, which focuses principally on using shallow (<100 m) stratigraphic drilling and coring to acquire the geologic data, is being led by the Antarctic Offshore Stratigraphy Project (ANTOSTRAT), a group that works under the aegis of the Scientific Committee on Antarctic Research (SCAR). About 40 scientists from 12 countries met this past summer in Wellington, New Zealand, at an ANTOSTRAT meeting to discuss strategies for implementing the desired paleoenvironmental field and modeling studies. The meeting was held in conjunction with the 8th International Symposium on Antarctic Earth Sciences.
Keywords: Antarktis; geologi; geovitenskap; klimatologi; paleontologi; stratigrafi

The impact of greenhouse gases and halogenated species on future solar UV radiation doses - Taalas, Petteri; Kaurola, Jussi; Kylling, Arve; Shindell, Drew; Sausen, Robert; Dameris, Martin; Grewe, Volker; Herman, Jay; Damski, Juhani; Steil, Benedikt (Geophysical Research Letters, 2000)
The future development of stratospheric ozone layer depends on the concentration of chlorine and bromine containing species. The stratosphere is also expected to be affected by future enhanced concentrations of greenhouse gases. These result in a cooling of the winter polar stratosphere and to more stable polar vortices which leads to enhanced chemical depletion and reduced transport of ozone into high latitudes. One of the driving forces behind the interest in stratospheric ozone is the impact of ozone on solar UV-B radiation. In this study UV scenarios have been constructed based on ozone predictions from the chemistry-climate model runs carried out by GISS, UKMO and DLR. Since cloudiness, albedo and terrain height are also important factors, climatological values of these quantities are taken into account in the UV calculations. Relative to 1979–92 conditions, for the 2010–2020 time period the GISS model results indicate a springtime enhancement of erythemal UV doses of up to 90% in the 60–90 °N region and an enhancement of 100% in the 60–90 °S region. The corresponding maximum increases in the annual Northern Hemispheric UV doses are estimated to be 14% in 2010–20, and 2% in 2040–50. In the Southern Hemisphere 40% enhancement is expected during 2010–20 and 27% during 2040–50.
Keywords: Antarktis; UV-stråling; drivhusgasser; klimaendringer; klimatologi; ozonlaget; polarområdene; ultrafiolett stråling